Positive electrode active material and secondary battery

By using fluoride molten salt in lithium cobalt oxide batteries to promote magnesium doping and combined with the doping of nickel and aluminum, the problem of degradation of performance of lithium cobalt oxide batteries at high cutoff voltage is solved, and higher cycling stability and safety are achieved.

CN119920859APending Publication Date: 2025-05-02SEMICON ENERGY LAB CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411496686.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-04-11
Filing Date
2024-10-25
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The performance of existing lithium cobalt oxide batteries decreases at high cutoff voltages, resulting in a decrease in capacity during the charge and discharge cycle and a collapse in the crystal structure.

Method used

By using the fluoride molten salt as an additive, magnesium is effectively fused to lithium cobalt oxide and combined with doping of nickel and aluminum, the electrochemical stability is improved.

Benefits of technology

Phase transition suppression at the cutoff voltage exceeding 4.55V is achieved, which extends the cycle life of lithium cobalt oxide batteries and improves the discharge capacity and battery safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920859A_ABST
    Figure CN119920859A_ABST
Patent Text Reader

Abstract

Provided are: a positive electrode active material in which phase transition is suppressed; and a secondary battery comprising the positive electrode active material. The present invention develops an unprecedented synthesis method in which a molten salt of MgF2-LiF is used as a reaction accelerator to treat lithium cobalt oxide particles, thereby facilitating diffusion and doping of magnesium into a lithium cobalt oxide block and forming a stable coating layer on the surface layer of the particles. It was confirmed by ex site XRD analysis that when the improved LiCoO2 is charged to 4.7 V, harmful phase transitions are suppressed and new phases appear. The improved LiCoO2 shows good electrochemical performance in high-voltage work. The technique provides a guide for suppressing basic deterioration accompanying phase transition to achieve an ultra-high energy density LiCoO2 positive electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] One embodiment of the present invention relates to an article, method or manufacturing method. In addition, the present invention relates to a process, machine, product or composition of matter. One embodiment of the present invention relates to a storage device including a secondary battery, a semiconductor device, a display device, a light-emitting device, a lighting device, an electronic device or a manufacturing method thereof.

[0002] Note that in this specification, electronic equipment refers to any device having a power storage device. An electro-optical device having a power storage device, an information terminal device having a power storage device, and the like are all electronic equipment. Background Art

[0003] The emergence of portable electronic devices such as smartphones and tablet terminals has greatly changed people's lives. With the continuous integration and strengthening of device functions, the demand for high-capacity secondary batteries continues to expand. Lithium cobalt oxide (LiCoO2, hereinafter also referred to as LCO) has always been the best candidate for high-capacity lithium-ion batteries widely used in mobile devices due to its good energy density. The theoretical capacity of lithium cobalt oxide is 274mAh / g. However, the battery performance decreases in the high delithiation state, that is, when charged with a high cut-off voltage. Therefore, recent lithium cobalt oxide-based products are forced to use the full battery at a cut-off voltage of 4.47V. The above potential of the full battery is equivalent to vs.Li + The potential in / Li is about 4.55V and the discharge capacity is 200mAh / g.

[0004] The reasons for the decrease in capacity during the charge and discharge cycle include side reactions on the surface of lithium cobalt oxide, dissolution of cobalt, oxygen release, changes in crystal structure and crack formation. In order to reduce the degradation under high cut-off voltage, various technologies such as element doping, surface coating, and improvement of electrolyte are applied to lithium cobalt oxide and secondary batteries containing lithium cobalt oxide (Non-Patent Documents 1 to 20).

[0005] Lithium cobalt oxide has an α-NaFeO2 (layered rock salt type) crystal structure of the R-3m space group, and belongs to the O3 phase characterized by the ABCABC stacking arrangement of oxygen. When lithium is extracted from lithium cobalt oxide at a high voltage, the lithium cobalt oxide transforms from the O3 phase to the H1-3 phase, and then to the O1 phase (note that the oxygen in the O1 phase is stacked in ABAB. The H1-3 phase is a mixture of the O1 phase and the O3 phase in which oxygen is stacked in ABABCACABCBC). This change is accompanied by a structural change equivalent to the deviation of the CoO2 layer, which causes stress in the crystal. This structural change can cause the formation of cracks and / or deterioration of crystallinity, which may lead to a decrease in the performance of batteries containing lithium cobalt oxide. Therefore, especially when the cut-off voltage exceeds 4.55V (vs.Li+ / Li), in order to achieve a stable charge and discharge cycle, it is extremely important to effectively prevent the phase transition from the O3 phase to the H1-3 phase. Generally speaking, the phase transition and volume change caused by the electrochemical insertion and separation of cations will lead to the degradation of electrochemical properties. Therefore, effectively alleviating the above phenomenon is not only important for the development of lithium cobalt oxide but also for the development of other positive electrode active materials.

[0006] [Non-patent document 1] Tukamoto, H. & West, A. Electron conductivity of LiCoO2 and its enhancement by magnesium doping. J. Electrochem. Soc. 144, 3164-3168 (1997). [Non-patent document 2] Bae, J Get al. Structural evolution of Mg-doped single-crystal LiCoO2 cathodes: importance of morphology and Mg-doping sites. ACSAppl.Mater.Interfaces 15, 7939-7948 (2023). [Non-patent document 3] Mladenov, M., Stoyanova, R., Zhecheva, E. & Vassilev, S. Effect of Mg doping and MgO-surface modification on the cycling stability of LiCoO2electrodes. Electrochem. Commun. 3, 410-416 (2001). [Non-patent document 4] Jang YI et al. Synthesis and characterization of LiAl y Co 1-y O2 and LiAl y Ni 1-y O2. J. Power Sources 81-82, 589-593 (1999). [Non-patent document 5] Luo, W. & Dahn, JR Comparative study of Li [Co1-zAlz]O2 prepared by solid-state and co-precipitation methods. Electrochim. Acta 54, 4655-4661 (2009). [Non-patent document 6] Liu, A., Li, J., Shunmugasundaram, R. & Dahn, JRSynthesis ofMg and Mn doped LiCoO2 and effects on high voltagecycling. J. Electrochem. Soc. 164, A1655-A1664 (2017). [Non-patent document 7] Zhang, J. Net al. Trace doping of multiple elements enables stable battery cycling of LiCoO2 at 4.6V. Nat. Energy 4, 594-603 (2019). [Non-patent document 8] Kong, W. et al. Unraveling the distinct roles of Mgoccupation on Li or Co sites on high-voltage LiCoO2. J. Electrochem. Soc. 168, 030528 (2021). [Non-patent document 9] Shim, JH., Lee, S. & Park, SSE effects of MgO coating on the structural and electrochemical characteristics of LiCoO2 as cathode materials for lithium ion battery. Chem. Mater. 26, 2537-2543 (2014). [Non-patent document 10] Cho, J., Kim, YJ & Park, B. Novel LiCoO2 cathode material with Al2O3 coating for a lithium cell. Chem. Mater. 12, 3788-3791 (2000). [Non-Patent Document 11] Lee, J.G., Kim, B., Cho, J., Kim, Y.W. & Park, B. Effect of AlPO4-nanoparticle coating concentration on high-cutoff-voltage electrochemical performances in LiCoO2. J. Electrochem. Soc. 151, A801 - A805 (2004). [Non-Patent Document 12] Qian, J. et al. Electrochemical surface passivation of LiCoO2 particles at ultrahigh voltage and its applications in lithium-based batteries. Nat. Commun. 9, 4918 (2018). [Non-Patent Document 13] Moon, S.H. et al. TiO2-coated LiCoO2 electrodes fabricated by a sputtering deposition method for lithium-ion batteries with enhanced electrochemical performance. RSC Adv. 9, 7903 - 7907 (2019). [Non-Patent Document 14] Taguchi, N., Akita, T., Tatsumi, K. & Sakaebe, H. Characterization of MgO-coated-LiCoO2 particles by analytical transmission electron microscopy. J. Power Sources 328, 161 - 166 (2016). [Non-Patent Document 15] He, Y. et al. A bi-functional strategy involving surface coating and subsurface gradient co-doping for enhanced cycle stability of LiCoO2 at 4.6V. J. Energy Chem. 77, 553 - 560 (2023). [Non-patent document 16] Orikasa, Y. et al. Origin of surface coating effect for MgO on LiCoO2 to improve the interfacial reaction between electrode and electrolyte. Adv. Mater. Interfaces 1, 1400195 (2014). [Non-patent document 17] Yang, X. et al. Pushing lithium cobalt oxides to 4.7V by lattice-matched interfacial engineering. Adv. Energy Mater. 12, 2200197 (2022). [Non-patent document 18] Takahashi, Y. et al. Structure and electron density analysis of electrochemically and chemically delithiated LiCoO2 singlecrystals. J. Solid State Chem. 180, 313-321 (2007). [Non-patent document 19] Chen, Z., Lu, Z. & Dahn, JRStagging phase transitions in Li x CoO2.J.Electrochem.Soc.149,A1604-A1609(2002). [Non-patent document 20] Van der Ven, A., Aydinol, MK, Ceder, G., Kresse, G. & Hafner, J. First-principles investigation of phase stability in Li x CoO2.Phys.Rev.B 58, 2975-2987(1998). [Non-patent document 21] Momma, K. & Izumi, F. VESTA3 for three-dimensional visualization of crystal, volumetric and morphology data. J. Appl. Crystallogr. 44, 1272-1276 (2011). Summary of the invention

[0007] Magnesium doping and coating can improve the electrochemical performance of lithium cobalt oxide at high voltage. Recent studies have shown that by doping Mg at the lithium site of lithium cobalt oxide 2+ Ions can act as pillars between adjacent CoO2 layers, thereby improving electrochemical performance (Non-Patent Document 14, Non-Patent Document 17, etc.) However, there is no technology that satisfies the electrochemical reversibility of lithium insertion and extraction under high voltage charging.

[0008] Therefore, one of the objects of one embodiment of the present invention is to provide a device having a cut-off voltage exceeding 4.55 V (vs. Li + / Li) under charge and discharge of the positive electrode active material having suppressed phase transition. In addition, one of the purposes of one embodiment of the present invention is to provide a positive electrode active material or composite oxide in which the discharge capacity decrease in the charge and discharge cycle is suppressed. In addition, one of the purposes of one embodiment of the present invention is to provide a positive electrode active material or composite oxide whose crystal structure is not easily collapsed even if the charge and discharge are repeated. In addition, one of the purposes of one embodiment of the present invention is to provide a positive electrode active material or composite oxide with large discharge capacity. In addition, one of the purposes of one embodiment of the present invention is to provide a secondary battery with high safety or reliability.

[0009] Another object of one embodiment of the present invention is to provide a positive electrode active material, a composite oxide, a power storage device, or a method for producing the same.

[0010] Note that the description of these objects does not prevent the existence of other objects. Note that one embodiment of the present invention does not necessarily achieve all of the above objects. Note that objects other than the above objects can be extracted from the description of the specification, drawings, and claims.

[0011] To achieve the above object, one embodiment of the present invention proposes a method for effectively fusing magnesium to lithium cobalt oxide by using a fluoride molten salt as an additive. In addition, by combining nickel and aluminum as additive elements, electrochemical stability is further improved.

[0012] The surface of the synthesized lithium cobalt oxide presents a magnesium-rich rock salt structure, forming a coherent bond with the bulk material. Through ex situ X-ray diffraction (XRD) analysis, it can be proved that the lithium cobalt oxide of one embodiment of the present invention does not transform into the H1-3 phase but transforms into the O3 phase compressed at 4.7V (referred to as the "O3' phase" in this specification, etc.). The capacity retention rates of the lithium cobalt oxide of one embodiment of the present invention after 100 cycles at cut-off voltages of 4.6V and 4.7V were 96.4% and 72.7%, respectively, showing very excellent results.

[0013] Furthermore, by using a mixture of a fluorine-substituted organic solvent and propane sultone as the solvent of the electrolytic solution, a secondary battery having better charge and discharge cycle characteristics even at a high cutoff voltage can be realized.

[0014] One embodiment of the present invention is a positive electrode active material comprising lithium cobalt oxide to which magnesium, fluorine, nickel and aluminum are added, wherein the positive electrode active material has a layered rock salt type crystal structure belonging to the space group R-3m in a discharged state, and in the layered rock salt type crystal structure in a discharged state, the lattice constant of the c-axis exceeds Moreover, the GOF (goodness-of-fit) when Rietveld refinement is performed by fitting LiCoO2 as the space group R-3m is less than 1.4, and the positive electrode active material includes a surface portion and a bulk region. The surface portion includes a magnesium-rich rock salt structure region, and the magnesium-rich rock salt structure region is continuously bonded to the bulk region.

[0015] In the above structure, the lattice constant of the c-axis is preferably less than

[0016] In addition, another embodiment of the present invention is a positive electrode active material comprising lithium cobalt oxide added with magnesium, fluorine, nickel and aluminum, wherein, in a spectrum measured by a narrow scan of Mg1s using an X-ray photoelectron spectroscopy, the bond energy representing the maximum strength of the positive electrode active material is between the bond energy representing the maximum strength of magnesium oxide and the bond energy representing the maximum strength of magnesium fluoride.

[0017] In the above structure, it is preferable that the bond energy showing the maximum intensity of the positive electrode active material in a spectrum measured by narrow scan of Mg1s using X-ray photoelectron spectroscopy exceeds 1303.3 eV and is less than 1306.3 eV.

[0018] In the above structure, when a cross section of the particle is analyzed by an electron probe microanalyzer, the Mg / Co (atomic ratio) of the positive electrode active material is preferably 0.005 to 0.015, and the Al / Co (atomic ratio) is preferably 0.005 or less.

[0019] In addition, another embodiment of the present invention is a positive electrode active material comprising lithium cobalt oxide to which magnesium, fluorine, nickel and aluminum are added, wherein the positive electrode active material has a layered rock salt type crystal structure belonging to the space group R-3m in a discharged state, and a battery in which the positive electrode active material, lithium metal and a mixture of 2 wt % vinylene carbonate mixed with lithium hexafluorophosphate, ethylene carbonate and diethyl carbonate are used as the positive electrode, the negative electrode and the electrolyte are respectively subjected to charge and discharge cycle tests at 25°C, and the positive electrode in the discharged state is analyzed by X-ray powder diffraction using CuKα1 rays, and the positive electrode has a 2θ value of 18.7. A peak appears in the range of 2θ being above 45.0° and below 45.3°, and its half width is below 0.12°. As a charge and discharge cycle test, the following charge and discharge cycle is repeated 100 times, that is, constant current charging is performed at a current value of 0.5C (note that 1C=200mA / g is satisfied) until the voltage is 4.7V, constant voltage charging is performed until the current value becomes 0.05C, and rest is performed for 10 minutes. Constant current discharge is performed at a current value of 0.5C until the voltage is 2.5V, and then rest is performed for 10 minutes.

[0020] In the above structure, preferably, the volume energy density calculated using the true density of the positive electrode active material is 4250 Wh / L or more, and the weight energy density calculated using the true density of the positive electrode active material is 865 Wh / kg or more.

[0021] In addition, another embodiment of the present invention is a secondary battery including the above-mentioned positive electrode active material and an electrolyte, wherein as the electrolyte, an electrolyte prepared by dissolving 1M LiPF6 in FEC / MTFP (volume ratio 2:8) and adding 5wt% of PS is used.

[0022] According to one embodiment of the present invention, a cut-off voltage exceeding 4.55V (vs. Li + / Li) is charged and discharged to suppress the phase transition caused by the positive electrode active material. In addition, according to one embodiment of the present invention, a positive electrode active material or composite oxide in which the discharge capacity decrease in the charge and discharge cycle is suppressed can be provided. In addition, according to one embodiment of the present invention, a positive electrode active material or composite oxide that is not easy to cause crystal structure collapse even if repeatedly charged and discharged can be provided. In addition, according to one embodiment of the present invention, a positive electrode active material or composite oxide with large discharge capacity can be provided. In addition, according to one embodiment of the present invention, a secondary battery with high safety or reliability can be provided.

[0023] Furthermore, according to one embodiment of the present invention, a positive electrode active material, a composite oxide, a power storage device, or a method for producing the same can be provided.

[0024] Note that the description of these effects does not prevent the existence of other effects. Note that one embodiment of the present invention does not necessarily have all of the above effects. Note that effects other than the above can be known and extracted from the description of the specification, drawings, claims, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Schematic diagram for explaining a method for producing a positive electrode active material according to one embodiment of the present invention and a surface and a bulk of the positive electrode active material; Figure 2 is a flow chart illustrating a process for producing a positive electrode active material according to one embodiment of the present invention; Figure 3A and Figure 3B is a graph showing DSC results; FIG. 4A to FIG. 4C is a graph showing DSC results; Figure 5A and Figure 5B is a graph showing DSC results; Figure 6 Schematic diagram for explaining phase transition of a positive electrode active material according to a comparative example and one embodiment of the present invention; Fig. 7A and Figure 7B is a diagram illustrating the computational model; FIG. 8A to FIG. 8C is a diagram illustrating the crystal structure of a positive electrode active material according to one embodiment of the present invention. Fig.8D and Fig. 8E is a diagram illustrating an example of lithium arrangement; 9A to 9E is a diagram illustrating an example of lithium arrangement; Fig.10 is a diagram illustrating an example of lithium arrangement; FIG. 11A to FIG. 11C is a diagram illustrating an example of lithium arrangement; Fig.12 is a diagram illustrating an example of lithium arrangement; FIG. 13A to FIG. 13D is a diagram illustrating a positive electrode according to one embodiment of the present invention; Fig.14A and Fig. 14B is a diagram illustrating a lithium ion battery according to one embodiment of the present invention; FIG. 15A to FIG. 15C is a diagram illustrating a lithium ion battery according to one embodiment of the present invention; FIG. 16A to FIG. 16D is a diagram for explaining a lithium-ion battery and a power storage system according to one embodiment of the present invention; FIG. 17A to FIG. 17C is a diagram illustrating a lithium ion battery according to one embodiment of the present invention; 18A to 18Cis a diagram illustrating a lithium ion battery according to one embodiment of the present invention; FIG. 19A to FIG. 19C is a diagram illustrating an electric vehicle according to one embodiment of the present invention; FIG. 20A to FIG. 20D is a diagram illustrating a transport vehicle according to one embodiment of the present invention; FIG. 21A to FIG. 21C It is a figure which illustrates a two-wheeled vehicle etc. according to one embodiment of the present invention; FIG. 22A to FIG. 22D It is a diagram for explaining an electronic device and the like according to one embodiment of the present invention; FIG. 23A to FIG. 23D is a diagram showing an example of a space device; FIG. 24A to FIG. 24C The XRD patterns of the positive electrode active materials of the comparative example and one embodiment of the present invention are shown; FIG. 25A to FIG. 25J SEM images, HAADF-STEM images, and nanobeam electron diffraction patterns of positive electrode active materials according to comparative examples and one embodiment of the present invention are shown; FIG. 26A to FIG. 26J SEM images and SEM-EDX mapping images of a positive electrode active material according to one embodiment of the present invention in each synthesis step are shown; FIG. 27A to FIG. 27F SEM images and SEM-EDX mapping images of a positive electrode active material according to one embodiment of the present invention in each synthesis step are shown; Fig.28 The XPS spectra of the positive electrode active materials of the comparative example and one embodiment of the present invention are shown; Fig.29A and Fig.29B The XPS spectra of the positive electrode active material according to one embodiment of the present invention in each synthesis step are shown; FIG. 30A to FIG. 30C A STEM-EDX element mapping image of the surface layer of a positive electrode active material according to one embodiment of the present invention and a graph showing the results of STEM-EDX line analysis; Fig.31 A STEM-EDX element mapping image of the surface layer of a positive electrode active material according to one embodiment of the present invention is shown; Fig.32A and Fig.32B The charge-discharge cycle characteristics of a half-cell including a comparative example and the charge-discharge cycle characteristics of a half-cell including a positive electrode active material according to one embodiment of the present invention are shown; Fig.33A and Fig.33B is a graph showing a charge-discharge curve and rate characteristics of a half-cell including a comparative example and a charge-discharge curve and rate characteristics of a half-cell including a positive electrode active material according to one embodiment of the present invention; Fig.34is a graph showing the rate characteristics of a half-cell including a comparative example and the rate characteristics of a half-cell including a positive electrode active material according to one embodiment of the present invention; Fig.35A and Fig.35B is a graph showing the charge-discharge cycle characteristics and charge-discharge curve of a half-cell including a comparative example and the charge-discharge cycle characteristics and charge-discharge curve of a half-cell including a positive electrode active material according to one embodiment of the present invention; Fig.36A and Fig.36B is a graph showing the charge and discharge cycle characteristics of a full battery including a positive electrode active material according to one embodiment of the present invention; FIG. 37A to FIG. 37C An ex situ XRD pattern of a positive electrode including a comparative example and an ex situ XRD pattern of a positive electrode including a positive electrode active material according to one embodiment of the present invention in a discharged state are shown; FIG. 38A to FIG. 38H SEM images of the positive electrode active material of the comparative example and one embodiment of the present invention after cycling are shown; Fig.39A and Fig.39B The SEM image shows the cycle characteristics of the positive electrode active material; FIG. 40A to FIG. 40D The HAADF-STEM image and nanobeam electron diffraction pattern of the surface layer of the comparative example after the charge-discharge cycle test and the HAADF-STEM image and nanobeam electron diffraction pattern of the surface layer of the positive electrode active material according to one embodiment of the present invention are shown; FIG. 41A to FIG. 41C An ex situ XRD pattern of a positive electrode including a positive electrode active material of a comparative example in a charged state is shown; FIG. 42A to FIG. 42C An ex situ XRD pattern of a positive electrode including a positive electrode active material according to one embodiment of the present invention in a charged state is shown; FIG. 43A to FIG. 43C An ex situ XRD pattern of a positive electrode including a positive electrode active material of a comparative example in a charged state is shown; FIG. 44A to FIG. 44C An ex situ XRD pattern of a positive electrode including a positive electrode active material according to one embodiment of the present invention in a charged state is shown; Fig.45 is a graph showing a dQ / dV curve of charge and discharge of a positive electrode active material according to one embodiment of the present invention; FIG. 46A to FIG. 46C An ex situ XRD pattern of a positive electrode including a comparative example and an ex situ XRD pattern of a positive electrode including a positive electrode active material according to one embodiment of the present invention in a charged state are shown; Fig.47A and Fig.47B is a graph showing the charge-discharge cycle characteristics of a half-cell including a comparative example and the charge-discharge cycle characteristics of a half-cell including a positive electrode active material according to one embodiment of the present invention; FIG. 48A to FIG. 48C is a graph showing an ex situ XRD pattern of a positive electrode including a comparative example and an ex situ XRD pattern of a positive electrode including a positive electrode active material according to one embodiment of the present invention in a charged state; Fig.49A and Fig.49B is a graph showing the charge-discharge cycle characteristics of a half-cell including a comparative example and the charge-discharge cycle characteristics of a half-cell including a positive electrode active material according to one embodiment of the present invention; Fig.50A and Fig.50B is a graph showing the charge and discharge cycle characteristics of a half-cell including a positive electrode active material of a comparative example; Fig.51A and Fig.51B is a graph showing the charge-discharge cycle characteristics of a half-cell including a comparative example and the charge-discharge cycle characteristics of a half-cell including a positive electrode active material according to one embodiment of the present invention; Fig.52A and Fig.52B is a graph showing the charge-discharge cycle characteristics of a half-cell including a comparative example and the charge-discharge cycle characteristics of a half-cell including a positive electrode active material according to one embodiment of the present invention; Fig.53 is a graph showing the volume energy density and weight energy density of the positive electrode active material of the comparative example and one embodiment of the present invention; Fig.54 An ex situ XRD pattern of a positive electrode including a positive electrode active material according to one embodiment of the present invention in a discharged state is shown; Fig.55A and Fig.55B An ex situ XRD pattern of a positive electrode including a positive electrode active material according to one embodiment of the present invention in a discharged state is shown; Fig.56 An ex situ XRD pattern of a positive electrode including a positive electrode active material according to one embodiment of the present invention in a charged state is shown; Fig.57A and Fig.57B An ex situ XRD pattern of a positive electrode including the positive electrode active material according to one embodiment of the present invention in a charged state is shown. DETAILED DESCRIPTION

[0026] The following describes an example of an embodiment of the present invention using drawings and the like. Note that the present invention should not be interpreted as being limited to the following example of an embodiment. The embodiment of the invention may be changed within the scope of the gist of the present invention.

[0027] In the drawings, the size, thickness of a layer, or a region may be exaggerated for clarity of description, and therefore, the present invention is not limited to the sizes in the drawings.

[0028] In addition, in this specification, for the sake of convenience, ordinal numbers such as first and second are added, but they do not indicate the order of processes or the order of stacking. Therefore, for example, "first" can be appropriately replaced with "second" or "third" for description. In addition, the ordinal numbers recorded in this specification and the like are sometimes inconsistent with the ordinal numbers used to specify one embodiment of the present invention.

[0029] In this specification, etc., the space group is represented by the short notation of the international symbol (or Hermann-Mauguin symbol). In addition, the Miller index is used to represent the crystal plane and the crystal orientation. In crystallography, the space group, crystal plane and crystal orientation are represented by a superscript horizontal bar on the number. Each face representing the crystal plane is represented by "()". (minus sign) is used to represent the space group, crystal plane and crystal direction, instead of attaching a superscript horizontal bar to the number. In addition, "[]" is used to represent the individual orientation of the orientation within the crystal, "<>" is used to represent the collective orientation of all equivalent orientations, "()" is used to represent the individual face of the crystal plane, and "{}" is used to represent the collective face with equivalent symmetry. In addition, in general, in order to facilitate the understanding of the structure, the trigonal system represented by the space group R-3m is sometimes represented by a composite hexagonal lattice of the hexagonal lattice. Sometimes (hkil) is used as the Miller index in addition to (hkl). Here i is -(h+k). In this specification, etc., unless otherwise stated, the crystal planes of the space group R-3m and the like are represented by a complex hexagonal lattice.

[0030] In this specification, when it is only recorded as "positive electrode active material", depending on the analysis method, sometimes multiple positive electrode active material particles are described, and sometimes one positive electrode active material particle is described. For example, the records of scanning transmission electron microscope-energy dispersive X-ray detector (STEM-EDX) line analysis, STEM-electron energy loss spectrum (STEM-EELS) and electron diffraction, unless otherwise specified, all describe one positive electrode active material particle. On the other hand, the records of X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), various mass spectrometry analyses, etc., all describe multiple positive electrode active material particles unless otherwise specified.

[0031] In this specification, the particle is not limited to a sphere (circular cross-sectional shape), and the cross-sectional shape of each particle may also be an ellipse, a rectangle, a trapezoid, a triangle, a quadrangle with curved corners, an asymmetric shape, etc., and each particle may also be amorphous. In addition, when simply referred to as a "particle", it includes primary particles and secondary particles.

[0032] In addition, when describing the characteristics of the particles of the positive electrode active material, it is not necessary for all particles to have such characteristics. For example, as long as 50% or more, preferably 70% or more, more preferably 90% or more of three or more randomly selected positive electrode active material particles have the following preferred characteristics, it can be said that the characteristics of the positive electrode active material and the secondary battery including the positive electrode active material are sufficiently improved.

[0033] The distribution of a certain element refers to the region where the element is continuously detected within a non-noise range by a certain continuous analysis method. The region where the element is continuously detected within a non-noise range can also be, for example, the region where the element is surely detected every time an analysis is performed.

[0034] Note that in this specification and the like, the added element is synonymous with a mixture and a part of the raw material.

[0035] In addition, the theoretical capacity of the positive electrode active material refers to the amount of electricity when all the lithium that can be inserted and removed in the positive electrode active material is removed. For example, the theoretical capacity of LiCoO2 is 274 mAh / g, the theoretical capacity of LiNiO2 is 275 mAh / g, and the theoretical capacity of LiMn2O4 is 148 mAh / g.

[0036] In addition, let x in the compositional formula represent the amount of lithium that can be inserted and removed remaining in the positive electrode active material. For example, x in Li x MO2 (where M is one or more selected from cobalt, nickel, and manganese). In the positive electrode active material of the secondary battery, x = (theoretical capacity - charge capacity) / theoretical capacity. For example, when a secondary battery using Li x MO2 as the positive electrode active material is charged to 219.2 mAh / g, it can be said that the positive electrode active material is represented as Li 0.2 MO2 or it can be said that x = 0.2. A smaller x in Li x MO2 means, for example, 0.1 < x ≤ 0.24. In addition, sometimes the amount of lithium removed from the positive electrode active material relative to the theoretical capacity is represented by the depth of charge. In this specification and the like, the depth of charge = 1 - x.

[0037] For example, when lithium cobaltate appropriately synthesized before being used for the positive electrode substantially satisfies the stoichiometric ratio, the lithium cobaltate is LiCoO2 and x = 1. In addition, the lithium cobaltate in the secondary battery at the end of discharge can also be said to be LiCoO2 and x = 1. Here, "end of discharge" means, for example, a state where the voltage becomes 3.0 V or 2.5 V or less at a current of 100 mA / g or less.

[0038] For calculating Li xThe charge capacity and / or discharge capacity of x in MO2 is preferably measured under conditions without or with little effect of decomposition by short circuit and / or electrolyte, etc. For example, data of a secondary battery in which the capacity changes sharply as if it were a short circuit cannot be used to calculate x.

[0039] In addition, the space group of the crystal structure is identified by XRD, electron diffraction, neutron diffraction, etc. Therefore, in this specification, etc., belonging to a certain space group or a space group means being identified as a certain space group.

[0040] In addition, when the configuration of anions is roughly close to cubic closest packing, it can be regarded as cubic closest packing. The cubic closest packed anion configuration refers to the following state: the anions of the second layer are configured on the gaps of the anions filled in the first layer, and the anions of the third layer are configured just on the gaps of the anions of the second layer but not just on the anions of the first layer. Therefore, the anions may not be strictly cubic lattices. In addition, in fact, crystallization has defects, so the analysis results may not be based on theory. For example, spots may also appear in the fast Fourier transform (FFT) pattern of the electron diffraction pattern or the transmission electron microscope (TEM: Transmission Electron Microscope) image, etc., at a position slightly different from the theoretical position. For example, when the orientation deviation from the theoretical position is less than 5 degrees or less than 2.5 degrees, it can be said that there is a cubic closest packing structure.

[0041] In addition, sometimes the positive electrode active material to which the additive element for improving conductivity and / or the additive element for stabilizing the crystal structure is added is referred to as a composite oxide, a positive electrode material, a positive electrode material for secondary batteries, etc. In addition, in this specification, etc., the positive electrode active material of one embodiment of the present invention preferably includes a compound. In addition, in this specification, etc., the positive electrode active material of one embodiment of the present invention preferably includes a composition. In addition, in this specification, etc., the positive electrode active material of one embodiment of the present invention preferably includes a composite.

[0042] Generally speaking, as the charging voltage of the secondary battery increases, the potential of the positive electrode also increases. The positive electrode active material of one embodiment of the present invention has a stable crystal structure even at a high charging voltage. The crystal structure of the positive electrode active material in the charged state is stable, so the reduction in charge and discharge capacity caused by repeated charge and discharge can be suppressed.

[0043] Note that unless otherwise specified, the materials (positive electrode active material, negative electrode active material, electrolyte, separator, etc.) included in the secondary battery in the state before degradation are described. In addition, the following situation is not referred to as degradation: the situation where the discharge capacity is reduced due to aging treatment and burn-in treatment in the stage of manufacturing the secondary battery. For example, the following situation can be referred to as the state before degradation: the situation with a discharge capacity of more than 97% of the rated capacity of a lithium-ion secondary single cell and a lithium-ion secondary battery pack (hereinafter also referred to as a lithium-ion secondary battery). When using lithium-ion secondary batteries for portable devices, the rated capacity is based on JIS C 8711:2019. When using lithium-ion secondary batteries other than the above, it is not limited to the above-mentioned JIS specifications, and is based on various JIS, IEC standards, etc. for electric vehicle propulsion and industrial use.

[0044] In addition, in this specification, etc., the state before deterioration of the material included in the secondary battery is sometimes referred to as an initial article or an initial state, and the state after deterioration (a state in which the discharge capacity is less than 97% of the rated capacity of the secondary battery) is sometimes referred to as an article in use or a state in use or a used article or a used state.

[0045] Implementation Method 1 In this embodiment, refer to Figures 1 to 12 A method for producing a positive electrode active material according to one embodiment of the present invention and characteristics of the positive electrode active material are described. Note that for clarity, the positive electrode active material according to one embodiment of the present invention may be referred to as MFNA-LCO based on the initial letters of the added elements.

[0046] The positive electrode active material of one embodiment of the present invention includes lithium cobalt oxide to which magnesium, fluorine, nickel, and aluminum are added. Note that the composition of lithium cobalt oxide (LCO, LiCoO2) is not strictly limited to Li:Co:O=1:1:2.

[0047] The positive electrode active material of one embodiment of the present invention has a layered rock salt type crystal structure belonging to the space group R-3m in the discharged state. The lattice constant of the c-axis of the crystal structure exceeds and less than The GOF of the positive electrode active material in the discharged state in the crystal structure analysis is preferably 2.0 or less, and more preferably 1.4 or less.

[0048] In order to keep the charge neutral during the insertion and extraction of lithium ions, the positive electrode active material of the lithium ion secondary battery preferably contains a transition metal that can be oxidized and reduced. Preferably, the positive electrode active material of one embodiment of the present invention mainly uses cobalt as a transition metal for redox reaction. When cobalt accounts for more than 95 atomic% of the transition metal contained in the positive electrode active material, preferably more than 98 atomic%, and more preferably more than 99 atomic%, it has many advantages such as being relatively easy to synthesize, easy to handle, and having good cycle characteristics, so it is preferred.

[0049] The positive electrode active material according to one embodiment of the present invention includes a surface layer portion and a bulk body and may have a grain boundary.

[0050] In this specification, etc., the surface portion of the positive electrode active material refers to the area within 10 nm perpendicular or approximately perpendicular to the bulk from the surface. Therefore, the surface portion includes the surface. Approximately perpendicular means more than 80° and less than 100°. The surface generated by the closed cracks and / or fissures can also be called the surface. The surface portion is synonymous with the vicinity of the surface, the area near the surface or the shell, including the outermost surface.

[0051] In addition, the region deeper than the surface layer of the positive electrode active material is called a bulk. The bulk is synonymous with the interior or the core.

[0052] In addition, the grain boundary refers to, for example: the part where the particles of the positive electrode active material are bonded together; the part where the crystal orientation changes inside the positive electrode active material, that is, the repeated discontinuous part of the bright lines and dark lines in the STEM image, the part containing multiple crystal defects, the part with a disordered crystal structure, etc. In addition, the crystal defect refers to the defect observable by the cross-sectional transmission electron microscope (TEM) image, the cross-sectional STEM image, etc., that is, the structure and voids where other atoms enter the lattice. The grain boundary can be said to be one of the surface defects. In addition, the vicinity of the grain boundary refers to the area from the grain boundary to within 10nm.

[0053] The surface layer of the positive electrode active material according to one embodiment of the present invention contains magnesium, fluorine, nickel, and aluminum as additive elements. The detected amount of the additive elements in the surface layer is preferably higher than that in the bulk.

[0054] In addition, when the positive electrode active material of one embodiment of the present invention has a grain boundary, it is preferred that at least a portion of magnesium, fluorine, nickel and aluminum as an additive element be included near the grain boundary. That is, the detected amount of the additive element near the grain boundary is preferably higher than that of the surface layer and the portion other than the grain boundary.

[0055] In addition, in the block of the positive electrode active material of one embodiment of the present invention, the preferred amount thereof is different depending on the added element. Magnesium is preferably present in a trace amount in the block to suppress the phase transition described later. Nickel is also preferably present in a trace amount in the block. However, fluorine and aluminum are preferably not present in the center of the block or are so little that they cannot be detected. This is because: in order to suppress the phase transition, it is necessary to add elements, but when too much of the added element is present in the block, there will be disadvantages such as decreased crystallinity and decreased charge and discharge capacity.

[0056] Therefore, when the bulk cross section of the positive electrode active material particles of one embodiment of the present invention is analyzed using an electron probe microanalyzer (EPMA), Mg / Co (atomic ratio) is preferably 0.005 or more and 0.015 or less. In addition, Ni / Co (atomic ratio) is preferably 0.002 or more and 0.05 or less, and more preferably 0.03 or more and 0.01 or less.

[0057] In addition, in the bulk, the F / Co (atomic ratio) is preferably 0.01 or less, and more preferably, no fluorine is detected. The Al / Co (atomic ratio) is preferably 0.005 or less, and more preferably, no aluminum is detected.

[0058] Lithium cobalt oxide is susceptible to thermal decomposition at temperatures above 950°C in air. However, magnesium oxide (MgO) has extremely high thermal stability and a melting point of 2852°C. When lithium cobalt oxide and magnesium oxide powder are heated at a temperature below the decomposition temperature of lithium cobalt oxide, the solid reaction in the existing mixing and calcining process also tends to be uneven and slow. Therefore, it is difficult to introduce magnesium into lithium cobalt oxide in the existing doping and coating techniques.

[0059] Therefore, the present inventors used fluoride molten salt to promote the diffusion and doping of magnesium into the lithium cobalt oxide bulk. In this method, while magnesium diffuses into the bulk, the surface of the lithium cobalt oxide particles is coated with excess magnesium.

[0060] Figure 1 It is a schematic diagram of a method for manufacturing a positive electrode active material of one embodiment of the present invention using a fluoride used as a reaction accelerator and a surface portion and a bulk of the positive electrode active material. The surface has a magnesium-rich rock salt structure region, which is coherently bonded to the bulk region. A schematic diagram of a coherent bonding structure is drawn using VESTA (non-patent document 21). By using a fluoride used as a reaction accelerator, efficient diffusion and doping of additive elements such as magnesium into the surface portion and bulk of lithium cobalt oxide particles can be achieved.

[0061] As the fluoride used as a reaction accelerator, it is preferred to use a fluoride of a typical metal element. For example, lithium fluoride (LiF), sodium fluoride (NaF) and potassium fluoride (KF) and a mixture thereof have a melting point close to the decomposition temperature of lithium cobalt oxide and lower than the decomposition temperature of lithium cobalt oxide, and are also highly safe, so they are preferred. In view of being used in lithium ion batteries, as a fluoride used as a reaction accelerator, it is particularly preferred to include lithium fluoride.

[0062] Figure 2 1 is a flow chart illustrating an example of a method for producing a positive electrode active material according to one embodiment of the present invention. In Example 1, six samples marked with asterisks in the accompanying drawings were analyzed by XPS and SEM-EDX. However, the present invention is not limited to Figure 2 The method shown in the figure. For example, the heating temperature and the heating time may be a temperature and a time sufficient to melt the fluoride used as a reaction accelerator without causing the lithium cobalt oxide to decompose. In addition, the most suitable range of the heating temperature and the heating time sometimes varies depending on the particle size of the raw material lithium cobalt oxide (hereinafter also referred to as pristine LCO or original LCO). In addition, the added elements may be added at other time sequences or may be added in multiple times. The time sequence may also be changed according to the element.

[0063] DSC Here, FIG. 3A to FIG. 5B The results of differential scanning calorimetry (DSC) are shown. DSC measurement was performed using Thermo Plus (EVO2 DSC8271, manufactured by Rigaku) ​​at a temperature increase rate of 20°C / min from room temperature to 1000°C. An alumina pan was used. As a reference Al2O3 powder was used.

[0064] Figure 3A The DSC results when MgF2 powder and LiF powder were mixed at a molar ratio of 3:1 are shown. The melting start temperature was 731.4°C and the melting peak temperature was 739.3°C. This result shows the eutectic point of MgF2 and LiF. Therefore, when exposed to the temperature proposed in this specification, etc. (e.g., 900°C), the above compound changes from a solid phase to a liquid phase and becomes a molten salt.

[0065] Figure 3B The DSC results of Mg(OH)2 powder are shown. The decomposition start temperature is 357.6°C and the maximum decomposition temperature is 418.8°C.

[0066] Figure 4A is the DSC measurement result of the original LCO powder. Figure 4B The DSC measurement results of a sample in which raw LCO, LiF and MgF2 powders were mixed at 1:0.003:0.01 (molar ratio) are shown. Figure 4C yes Figure 4BThe initial reaction temperature is 778.6°C and the peak reaction temperature is 814.5°C. These temperatures are slightly lower than the decomposition temperature of lithium cobalt oxide. Figure 3A The eutectic point of MgF2 and LiF is high (731.4°C), which means that the surface of lithium cobalt oxide particles reacts with the liquid containing magnesium fluoride.

[0067] Figure 5A The DSC results are shown when the powders of pristine LCO and Mg(OH)2 were mixed at 1:0.01 (molar ratio). Figure 5B yes Figure 5A The reaction onset temperature was 345.0°C and the reaction peak temperature was 363.9°C.

[0068] like Figure 5A and Figure 5B As shown in the DSC results of the mixture of original LCO and Mg(OH)2, an endothermic peak was observed at 363.9°C. This temperature is consistent with that in Figure 3B The decomposition temperature of the Mg(OH)2 monomer observed in the experiment is roughly the same (357.6°C), and no peak indicating the eutectic point of the original LCO and Mg(OH)2 is observed.

[0069] In such Figure 2 During the heating process in the manufacturing process shown, the surface of the lithium cobalt oxide particles and the fluoride molten salt are partially melted, and the additive elements such as magnesium are efficiently diffused and doped. As a result, the phase change accompanying the deviation of the CoO2 layer is suppressed, and the structure of the positive electrode active material in a highly delithiated state of one embodiment of the present invention is different from that of the original LCO.

[0070] Figure 6 1 is a diagram illustrating the phase transition of the original LCO and the positive electrode active material of one embodiment of the present invention. It is known that LCO is charged to 4.55V (Li x When x < 0.3 in CoO2), a phase transition from O3 phase to H1-3 phase occurs. This phase transition is accompanied by a structural change equivalent to the deviation of the CoO2 layer. In addition, the volume difference between the above two crystal structures is also large. When compared with the same number of cobalt atoms, the volume difference between the H1-3 phase in the charged state and the lithium cobalt oxide (O3 phase) in the discharged state exceeds 3.5%, typically more than 3.9%.

[0071] However, when the positive electrode active material of one embodiment of the present invention is in a highly delithiated state, the magnesium substituted in the lithium layer becomes a structural support, thereby preventing the CoO2 layer from deviating, thereby suppressing the phase transition from the O3 phase to the H1-3 phase. Furthermore, the deviation probably starts from the surface of LCO, and may be suppressed by the presence of a magnesium-rich rock salt region in the surface layer of the positive electrode active material of one embodiment of the present invention.

[0072] The positive electrode active material of one embodiment of the present invention is 4.7V (vs. Li + / Li) does not transform into the H1-3 phase, but transforms into a phase referred to as the O3' phase in this specification, etc.

[0073] The crystal structure of the O3' phase belongs to the space group R-3m. The coordinates of cobalt and oxygen in the unit cell can be represented by Co(0,0,0.5) and O(0,0,x), where 0.20≤x≤0.22. In addition, the lattice constant of the unit cell is as follows: a-axis Preferably More preferably Typically c-axis Preferably More preferably Typically

[0074] In the O3' phase, ions such as cobalt, nickel, and magnesium occupy the positions coordinated to six oxygen atoms. In addition, light elements such as lithium and magnesium sometimes occupy the positions coordinated to four oxygen atoms.

[0075] In addition, the volume difference of the same number of cobalt atoms in the O3 phase and the O3' phase in the discharged state is 2.5% or less, specifically 2.2% or less, and typically 1.8%.

[0076] In addition, since the positive electrode active material of one embodiment of the present invention uses fluoride as a reaction accelerator, it is preferred to detect fluorine in the surface analysis of the positive electrode active material. For example, fluorine is preferably detected by X-ray photoelectron spectroscopy (XPS). And, as an element indicating that the fluoride has passed through the molten salt stage, it is preferred to show a bond energy different from that of the compound used as a material.

[0077] For example, in the spectrum of the narrow scan measurement of Mg1s of the positive electrode active material of one embodiment of the present invention obtained by XPS, it is preferred to show a maximum value different from the bond energy of magnesium oxide and magnesium fluoride. More specifically, in the narrow scan spectrum of Mg1s of the positive electrode active material of one embodiment of the present invention, it is preferred to show a maximum value between the bond energy of magnesium oxide and magnesium fluoride.

[0078] Since the positive electrode active material of one embodiment of the present invention suppresses the harmful phase transition associated with the deviation of the CoO2 layer, even after 4.7V (vs. Li + / Li) in a high cut-off voltage charge-discharge cycle test, the crystal structure deteriorates very little.

[0079] Specifically, after a charge and discharge cycle test on a battery using a positive electrode active material of one embodiment of the present invention, lithium metal, and a mixture of 2wt% of vinylene carbonate mixed with lithium hexafluorophosphate, ethylene carbonate, and diethyl carbonate as the positive electrode, negative electrode, and electrolyte respectively under a 25°C environment, the positive electrode in the discharged state was analyzed by X-ray powder diffraction using CuKα1 rays, and a peak appeared in the range of 2θ being greater than 18.7° and less than 19.0°, and its half width was less than 0.10°, more preferably less than 0.08°, and a peak appeared in the range of 2θ being greater than 45.0° and less than 45.3°, and its half width was less than 0.12°, more preferably less than 0.09°. As a charge and discharge cycle test at this time, the following charge and discharge cycle was repeated 100 times, that is, constant current charging was performed at a current value of 0.5C (note, 1C = 200mA / g) until the voltage reached 4.7V, constant voltage charging was performed until the current value reached 0.05C, and then rested for 10 minutes, and constant current discharge was performed at a current value of 0.5C until the voltage reached 2.5V, and then rested for 10 minutes.

[0080] Since it can withstand the charge and discharge cycle test under high cut-off voltage, a high energy density positive electrode can be realized by using the positive electrode active material of one embodiment of the present invention, and a secondary battery can be realized. For example, the volume energy density calculated using the true density of the positive electrode active material can be 4250Wh / L or more, and the weight energy density calculated using the true density of the positive electrode active material can be 865Wh / kg or more.

[0081] "calculate" To obtain evidence for the mechanism that prevents the phase transition to the H1-3 phase, first principle calculations were performed.

[0082] Models were created in which all lithium was removed from a lithium layer, depending on the case where the oxygen stack was in the O3 phase or the H1-3 phase. In addition, models were created in which magnesium was added to the layer from which lithium was removed, depending on the O3 phase stacking or the H1-3 phase stacking. These models were optimized for structure including unit size, and their energies were compared.

[0083] The calculations were performed using the density functional theory (DFT) software "VASP" with the PAW method installed. In the calculations, structural optimization including the unit size was performed. GGA-PBE was used as the exchange correlation interaction. The spin degrees of freedom were not considered. To correct for dispersion interactions, the DFT-D3 (BJ) method using the Becke-Johnson damping function was used. The cutoff energy was 1000 eV and the k-point sampling was 3×3×3. In the calculation of the electronic state, when the energy change was less than 10 -8eV is considered converged. In addition, in structural optimization, when all forces become less than Stop structural relaxation.

[0084] As calculation models, the model in which the CoO2 layer in LiCoO2 is O3 phase stacking (O3 phase stacking model) and the model in which the CoO2 layer is H1-3 phase stacking (H1-3 phase stacking model) are used as basic models. In the above two basic models, there is a stacked structure of Li layer, CoO2 layer, Li layer, and CoO2 layer in the unit used for calculation. The number of atoms in the unit is as follows: Li is 24, Co is 24, and O is 48. Models are made based on the above two models, that is, all Li in one Li layer is removed and four of the 12 Li in another Li layer are retained. The two models obtained are Mg-free models. The model in which a Mg atom is added to the layer in which all Li is removed from the above Mg-free model is called a Mg-containing model. Finally, four models of "Mg-free O3 phase stacking model", "Mg-free H1-3 phase stacking model", "Mg-containing O3 phase stacking model" and "Mg-containing H1-3 phase stacking model" are made.

[0085] The four models were subjected to structural optimization including cell size and the energies were compared. Fig. 7A and Figure 7B The "O3 phase stacking model with Mg" and the "H1-3 phase stacking model with Mg" after structural optimization including unit size are shown. In addition, Table 1 shows the energy of the four models. Here, E(H1-3) and E(O3) represent the energy of the H1-3 phase stacking model and the energy of the O3 phase stacking model, respectively.

[0086] [Table 1]

[0087] The energy of H1-3 phase stacking is lower in the model without magnesium, while the energy of O3 phase stacking is lower in the model with magnesium. This result shows that the presence of magnesium makes H1-3 phase stacking difficult. In the O3 phase stacking model containing magnesium, cobalt does not exist above and below magnesium, but in the H1-3 phase stacking, cobalt exists above and below magnesium. It can be considered that the energy of the H1-3 phase stacking model containing magnesium becomes higher due to the electrostatic repulsion between magnesium and the upper and lower cobalt. In addition, it can be considered that magnesium increases the barrier when the CoO2 layer deviates.

[0088] The above calculations show that magnesium functions as a pillar to prevent the phase transition to the H1-3 phase.

[0089] Li's Order For example, the coordinates of cobalt and oxygen in the O3' phase can be determined by performing ex situ XRD measurement. On the other hand, the X-ray scattering energy of lithium is low, so it is impossible to analyze whether the lithium contained in the O3' phase is ordered or disordered by XRD. For example, Fig. 8A This is a diagram of the crystal structure model of the O3' phase viewed from the a-axis direction. Figure 8B 1 and 2 are diagrams showing a crystal structure model of the O3′ phase viewed from the c-axis direction. In these drawings, it is assumed that lithium exists at all lithium positions with the same probability.

[0090] However, it is possible that the lithium is actually ordered in the O3' phase, and it may be possible to determine the lithium arrangement by simultaneous structural analysis using other methods such as neutral diffraction. FIG. 8D to FIG. 12 This shows that the LiO3' phase contains an orderly Li x Examples of x and lithium arrangement in CoO2. These figures are all diagrams of the crystal structure model of the O3' phase viewed from the c-axis direction. FIG. 8D to FIG. 10 and Fig.12 In the figure, for the sake of clarity, the lithium positions are represented by the vertices of the regular triangles and the lithium is represented by the shaded circles. For reference, Figure 8C Show that Figure 8B The same graph is superimposed with a graph in which the vertices of the regular triangles represent the positions of lithium.

[0091] Fig.8D It is shown that the O3' phase is Li 1 / 3 An example of lithium arrangement in a lithium layer that can be imagined in CoO2. In the following figures, the shaded parallelogram represents the smallest unit of repetition.

[0092] Fig. 8E It is shown that the O3' phase is Li 1 / 4 CoO2 is an example of lithium arrangement in one of the conceivable lithium layers.

[0093] Fig. 9A It is shown that the O3' phase is Li 2 / 9 CoO2 is an example of lithium arrangement in one of the conceivable lithium layers.

[0094] Fig. 9B , Fig. 9C , Fig.9D and Fig.9E It is shown that the O3' phase is Li 1 / 6 CoO2 is an example of lithium arrangement in one of the conceivable lithium layers.

[0095] Fig.10 It is shown that the O3' phase is Li 1 / 4This is an example of the arrangement of lithium in a certain three-layer continuous lithium layer that can be imagined in CoO2. For the sake of clarity, in the equilateral triangle whose vertices represent the positions of lithium, the first layer is represented by a solid line, the second layer is represented by a dotted line, and the third layer is represented by a thin solid line, and lithium existing in the same lithium layer is represented by the same hatching. Fig.10 It can also be said to be stacked three Fig. 8E And the diagram when viewed from the c-axis direction.

[0096] Fig.11A , Fig. 11B and Fig. 11C It is shown that the O3' phase is Li 1 / 6 This is an example of the arrangement of lithium in a certain continuous three-layer lithium layer that can be imagined in CoO2. In order to distinguish the lithium existing in each layer, the lithium existing in the same lithium layer is connected by a line. FIG. 11A to FIG. 11C It can be said to be stacked three times Fig.9D Three examples of when.

[0097] exist Figures 10 to 11C In the example in which lithium exists in all lithium layers of the O3' phase, the possible arrangement of lithium is not limited to this. It can be considered that layers containing lithium and layers not containing lithium appear alternately between repeated CoO2 layers.

[0098] Fig.12 It is shown that the O3' phase is Li 1 / 8 This is an example of a lithium arrangement in a certain four-layer lithium layer that can be imagined in CoO2. The first layer is represented by a solid line, the second layer is represented by a dotted line, the third layer is represented by a thin solid line, and the fourth layer is represented by a dotted line. Fig.12 Shown in the first and third layers with Fig. 8E The same arrangement includes an example of lithium and the second and fourth layers do not include lithium.

[0099] Note that the arrangement of lithium within the lithium layer surface and the arrangement in the c-axis direction are not limited to the above arrangement.

[0100] Note that in this specification, etc., the surface of the positive electrode active material refers to the surface of lithium cobalt oxide doped with magnesium or the like. Therefore, the positive electrode active material of one embodiment of the present invention does not include: a material to which a metal oxide such as aluminum oxide (Al2O3) that does not contain a lithium site that is helpful for charging and discharging is attached; a carbonate, a hydroxyl group, etc. that is chemically adsorbed after the positive electrode active material is manufactured. In addition, the attached metal oxide refers to, for example, a metal oxide whose crystal structure is different from that of lithium cobalt oxide.

[0101] In addition, the electrolyte, organic solvent, binder, conductive material or compounds derived from these materials that adhere to the positive electrode active material are also not included.

[0102] The positive electrode active material of one embodiment of the present invention is a compound containing transition metals and oxygen in which lithium can be embedded and detached, so the interface between the region where cobalt and oxygen are oxidized and reduced as lithium is embedded and detached and the region where cobalt and oxygen are not present is called the surface of the positive electrode active material. In addition, the surface generated by sliding, closing cracks and / or cracks may also be referred to as the surface of the positive electrode active material. When analyzing the positive electrode active material, the surface is sometimes covered with a protective film, but the protective film is not included in the positive electrode active material. As a protective film, a single layer or multilayer film of carbon, metal, oxide, resin, etc. is sometimes used.

[0103] Therefore, the position of the surface of the positive electrode active material in STEM-EDX analysis or the like means that the detected amount of characteristic X-rays of cobalt is the average value of the detected amount of characteristic X-rays of cobalt inside. AVE The average value of the detected amount of characteristic X of cobalt and the background Co BG The point where 50% of the total or the detected amount of characteristic X-rays of oxygen is the average value of the detected amount of characteristic X-rays of oxygen inside O AVE The average value of the detected amount of characteristic X-rays of oxygen and the background O BG In addition, it can be considered that the difference between the point where the detected amount of cobalt characteristic X-rays is 50% of the sum of the average value of the detected amount of cobalt characteristic X-rays inside and the average value of the detected amount of cobalt characteristic X-rays in the background and the point where the detected amount of oxygen characteristic X-rays is 50% of the sum of the average value of the detected amount of oxygen characteristic X-rays inside and the average value of the detected amount of oxygen characteristic X-rays in the background is caused by the influence of metal oxides, carbonates, etc. containing oxygen attached to the surface, so the detected amount of cobalt characteristic X-rays can be taken as the average value of the detected amount of cobalt characteristic X-rays inside. AVE The average value of the detected amount of characteristic X-rays of cobalt and the background Co BG The point where the sum is 50% is taken as the position of the surface of the positive electrode active material.

[0104] The average value of the detected amount of characteristic X-rays of cobalt in the background is Co BG For example, the detection amount of characteristic X-rays of cobalt can be avoided near the part where the detection amount of characteristic X-rays of cobalt begins to increase and the detection amount of characteristic X-rays within the range of 2 nm or more, preferably 3 nm or more outside the part can be averaged to obtain the average value Co of the detection amount of characteristic X-rays of cobalt inside. AVE It can be obtained by averaging the detected amount in a range of 2 nm or more, preferably 3 nm or more, from the region where the detected amount of characteristic X-rays of cobalt and oxygen is saturated and stable, such as from the region where the detected amount of characteristic X-rays of cobalt begins to increase to a depth of 30 nm or more, preferably to a portion exceeding 50 nm. The average value of the detected amount of characteristic X-rays of oxygen in the background is O BGand the average value of the detection amount of characteristic X-rays of oxygen inside AVE It can also be found in the same way.

[0105] In order to improve the spatial resolution of STEM-EDX line analysis, the beam diameter (also called beam diameter, probe diameter or probe diameter) of the electron beam is preferably small. The beam diameter in STEM-EDX line analysis is preferably 0.3 nm or less, more preferably 0.2 nm or less, and further preferably 0.1 nm or less.

[0106] In addition, the surface of the positive electrode active material in the cross-sectional STEM (scanning transmission electron microscope) image, etc. refers to: the boundary of the region where the image of the crystal structure derived from the positive electrode active material is observed and the region where the image is not observed, and refers to the outermost side of the region where the atomic column of the atomic nucleus of the metal element with an atomic number greater than lithium in the metal element constituting the positive electrode active material is confirmed. Alternatively, the surface of the positive electrode active material refers to: the intersection of the tangent drawn from the surface to the distribution of the brightness of the bulk in the STEM image and the axis in the depth direction. The surface in the STEM image, etc. can also be judged by referring to an analysis with a higher spatial resolution.

[0107] In addition, the spatial resolution of STEM-EDX is about 1 nm. Therefore, it is possible that the maximum value of the additive element distribution also deviates by about 1 nm. For example, when the maximum value of the additive element distribution such as magnesium is located outside the surface calculated above, as long as the difference between the maximum value and the surface is less than 1 nm, it can be regarded as an error.

[0108] In addition, the peak in STEM-EDX line analysis refers to the maximum value of the detection intensity in each element distribution or the maximum value of the characteristic X-ray of each element. As noise in STEM-EDX line analysis, the measured value of the half width below the spatial resolution (R), for example, below R / 2, is considered.

[0109] By scanning the same part multiple times under the same conditions, the influence of noise can be reduced. For example, the cumulative value of six scans can be used as the distribution of each element. The number of scans is not limited to six, and more than six scans can be performed and the average is used as the distribution of each element.

[0110] STEM-EDX line analysis can be performed, for example, by the following steps: First, a protective film is deposited on the surface of the positive electrode active material by evaporation, for example, by evaporating carbon using an ion sputtering device (MC1000 manufactured by Hitachi High-Technologies Corporation).

[0111] Next, the positive electrode active material is thinned to produce a STEM cross-sectional sample. For example, thinning can be performed by a FIB-SEM device (XVision200TBS manufactured by Hitachi High-Technologies Corporation). At this time, MPS (microprobe system) is used for picking up, and the final processing conditions are, for example, an acceleration voltage of 10 kV.

[0112] STEM-EDX line analysis uses, for example, a STEM device (HD-2700 manufactured by Hitachi High-Technologies Corporation), and as an EDX detector, an Octane TUltra W manufactured by EDAX Corporation (two are provided). When performing EDX line analysis, the emission current of the STEM device is set to 6 μA or more and 10 μA or less, and the shallow depth and less uneven part of the thin-sectioned sample is measured. The magnification is, for example, about 150,000 times. The conditions for EDX line analysis are as follows: drift correction; line width of 42 nm; pitch of 0.2 nm; number of frames of six or more.

[0113] In addition, when the surface layer contains both magnesium and nickel, it is possible that divalent nickel is more stably present near divalent magnesium. Therefore, even in a highly delithiated state, the dissolution of magnesium can be suppressed. This helps stabilize the surface layer.

[0114] For the same reason, in the manufacturing process, it is preferred to add magnesium before the process of adding nickel when adding additive elements to lithium cobalt oxide. Alternatively, it is preferred to add magnesium and nickel in the same process. Magnesium has a large ion radius and is likely to remain in the surface of lithium cobalt oxide regardless of which process it is added in. In contrast, when magnesium is not present, nickel is likely to diffuse widely into the interior of lithium cobalt oxide. Therefore, when nickel is added before magnesium is added, nickel diffuses into the interior of lithium cobalt oxide and may not remain in the surface in an appropriate amount.

[0115] In addition, when different additional elements are included in the depth direction, the crystal structure of a wider area can be stabilized, so it is preferred. For example, in the positive electrode active material of one embodiment of the present invention, the maximum value of the magnesium and nickel detection amount in the surface part is preferably different from the maximum value of the aluminum detection amount in the depth direction. In addition, it is preferred that the maximum value of the aluminum detection amount is present inside the particle compared to the maximum value of the magnesium and nickel detection amounts.

[0116] By having the distribution of the above-mentioned added elements, the crystal structure of a wider area can be stabilized. In this way, when magnesium, nickel and aluminum are simultaneously contained, since magnesium and nickel can fully stabilize the surface part, aluminum on the surface is not necessary. On the contrary, aluminum is preferably widely distributed in deeper areas. Aluminum is preferably continuously detected in an area with a depth of more than 1nm and less than 25nm from the surface. When it is widely distributed in an area with a depth of more than 0nm and less than 100nm from the surface, preferably in an area with a depth of more than 0.5nm and less than 50nm from the surface, the crystal structure of a wider area can be stabilized, so it is preferred.

[0117] When a plurality of additive elements are contained as described above, each additive element acts synergistically and contributes to further stabilization of the surface layer portion.

[0118] In addition, the added elements, i.e. magnesium, fluorine, nickel and aluminum, are preferably dissolved in the positive electrode active material. Therefore, for example, when performing line analysis of STEM-EDX, the depth at which the detected amount of the added elements increases is preferably located deeper than the depth at which the detected amount of cobalt increases, i.e., the inner side of the positive electrode active material.

[0119] In this specification, etc., the depth at which the detection amount of a certain element increases in line analysis by STEM-EDX means a depth at which a measurement value can be continuously obtained, and this measurement value can be determined not to be noise from the viewpoint of intensity and spatial resolution.

[0120] This embodiment mode can be combined with the contents of other embodiment modes as appropriate.

[0121] Implementation Method 2 In this embodiment, the structure of a lithium ion battery is described.

[0122] [positive electrode] The positive electrode includes a positive electrode active material layer and a positive electrode current collector. The positive electrode active material layer contains a positive electrode active material and may further contain at least one of a conductive auxiliary agent and a binder. As the positive electrode active material, the material described in the above embodiment can be used.

[0123] Fig.13A An example of a schematic diagram showing a cross section of a positive electrode is shown.

[0124] The current collector 550 may be, for example, a metal foil. The positive electrode may be formed by applying the slurry on the metal foil and drying it. Alternatively, the slurry may be pressed after drying. In the positive electrode, an active material layer is formed on the current collector 550.

[0125] The slurry is a material liquid used to form an active material layer on the current collector 550, and includes an active material, a binder, and a solvent, and preferably also contains a conductive additive. The slurry is sometimes referred to as an electrode slurry or an active material slurry. The positive electrode slurry is used when forming a positive electrode active material layer, and is sometimes referred to as a negative electrode slurry when forming a negative electrode active material layer.

[0126] The positive electrode active material 561 has the function of absorbing lithium ions and / or releasing lithium ions with charge and discharge. As a positive electrode active material 561 used in one embodiment of the present invention, a material with less degradation accompanying charge and discharge even when a high charge voltage is used. In this specification, etc., in the absence of special instructions, the charge voltage is expressed as a reference to the potential of lithium metal. In this specification, etc., a high charge voltage refers to, for example, a charge voltage of 4.6V or more, preferably 4.65V or more, more preferably 4.7V or more, further preferably 4.75V or more, and most preferably 4.8V or more.

[0127] As the positive electrode active material 561 used in one embodiment of the present invention, any material can be used as long as it is a material that has little degradation accompanying charge and discharge even when a high charging voltage is used, and the material described in Embodiment 1 can be used. In addition, as long as the positive electrode active material 561 is a material that has little degradation accompanying charge and discharge even when a high charging voltage is used, two or more materials with different particle sizes can be used.

[0128] The conductive aid is also called a conductive agent or a conductive material, and a carbon material can be used. By attaching the conductive aid between multiple active materials, multiple active materials are electrically connected to each other and the conductivity is improved. Note that in this specification, "attachment" not only refers to the physical close contact between the active material and the conductive aid, but also refers to the concept including the following situations: the situation where a covalent bond occurs; the situation where the Van der Waals force is bonded; the situation where the conductive aid covers a part of the surface of the active material; the situation where the conductive aid is embedded in the surface unevenness of the active material; the situation where they are electrically connected without contact, etc.

[0129] Specific examples of carbon materials that can be used as the conductive auxiliary agent include carbon black (furnace black, acetylene black, graphite, etc.).

[0130] Fig.13A Carbon black 553 is shown as a conductive auxiliary agent.

[0131] In order to fix the current collector 550 such as metal foil and the active material, the positive electrode of the lithium-ion battery can also be mixed with a binder (resin). The binder is also called a bonding agent. The binder is a polymer material. When a large amount of binder is included, the proportion of active material in the positive electrode decreases and the discharge capacity of the lithium-ion battery decreases. Therefore, it is preferred to mix the amount of binder to a minimum. Fig.13AIn FIG. 5 , the region not filled with the positive electrode active material 561 , the second active material 562 , and the carbon black 553 refers to a gap or a binder.

[0132] Fig.13A The example in which the positive electrode active material 561 is spherical is shown, but there is no particular limitation on the shape. The cross-sectional shape of the positive electrode active material 561 may be, for example, an ellipse, a rectangle, a trapezoid, a cone, a polygon with an arcuate corner, or an asymmetric shape. For example, Fig. 13B An example is shown in which the positive electrode active material 561 has a polygonal shape with rounded corners.

[0133] In addition, Fig. 13B In the positive electrode, graphene 554 is used as a carbon material used as a conductive auxiliary agent. Fig. 13B In the embodiment, a positive electrode active material layer including a positive electrode active material 561 , graphene 554 , and carbon black 553 is formed on the current collector 550 .

[0134] Note that in the step of mixing the graphene 554 and the carbon black 553 to obtain the electrode slurry, the weight of the mixed carbon black is preferably 1.5 times or more and 20 times or less, and preferably 2 times or more and 9.5 times or less, that of the graphene.

[0135] When the mixing of graphene 554 and carbon black 553 is set within the above range, the dispersion stability of carbon black 553 is excellent when adjusting the slurry, and it is not easy to generate an aggregation part. In addition, when the mixing of graphene 554 and carbon black 553 is set within the above range, a high electrode density can be achieved compared with a positive electrode in which only carbon black 553 is used as a conductive auxiliary agent. By increasing the electrode density, the capacity per unit weight can be increased. Specifically, the density of the positive electrode active material layer measured by weight can be 3.5 g / cc or more.

[0136] Compared with the positive electrode using only graphene as a conductive aid, the electrode density is low, but the mixing of the first carbon material (graphene) and the second carbon material (acetylene black) is within the above range, thereby enabling correspondingly fast charging. Therefore, this is particularly effective when used for automotive lithium-ion batteries.

[0137] exist Fig. 13C , an example of a positive electrode using carbon fiber 555 instead of graphene is shown. Fig. 13C Shown with Fig. 13B Different example: By using carbon fiber 555, aggregation of carbon black 553 can be prevented and dispersibility can be improved.

[0138] Note that Fig. 13C In the figure, the region not filled with the positive electrode active material 561, the carbon fiber 555, and the carbon black 553 refers to a void or a binder.

[0139] Fig.13D Other examples of positive electrodes are shown. Fig. 13C An example is shown in which carbon fibers 555 are used in addition to graphene 554. By using both graphene 554 and carbon fibers 555, aggregation of carbon black such as carbon black 553 can be prevented, and thus dispersibility can be further improved.

[0140] Note that Fig.13D In the figure, the region not filled with the positive electrode active material 561, the carbon fiber 555, the graphene 554, and the carbon black 553 refers to a gap or an adhesive.

[0141] Lithium-ion batteries can be manufactured by the following steps: FIG. 13A to FIG. 13D Any positive electrode in the stack, a separator is stacked on the positive electrode, and the stacked body in which the negative electrode is stacked on the separator is placed in a container (an outer packaging body, a metal can, etc.) and the container is filled with a liquid electrolyte (also called an electrolyte solution).

[0142] <Adhesive> As the adhesive, for example, preferably used are rubber materials such as styrene-butadiene rubber (SBR), styrene-isoprene-styrene rubber, acrylonitrile-butadiene rubber, butadiene rubber, ethylene-propylene-diene copolymer, etc. Fluorine rubber can also be used as the adhesive.

[0143] <Positive Electrode Current Collector> As the current collector, materials with high conductivity such as stainless steel, gold, platinum, aluminum, titanium and other metals and their alloys can be used. In addition, the material used for the positive electrode current collector is preferably not dissolved due to the potential of the positive electrode. In addition, aluminum alloys to which elements such as silicon, titanium, neodymium, scandium, molybdenum, etc. that improve heat resistance are added can be used. In addition, metal elements that react with silicon to form silicides can also be used. As metal elements that react with silicon to form silicides, there are zirconium, titanium, hafnium, vanadium, niobium, tantalum, chromium, molybdenum, tungsten, cobalt, nickel, etc. As the current collector, shapes such as foil, plate, sheet, mesh, punched metal mesh, and drawn metal mesh can be appropriately used. The thickness of the current collector is preferably 5 μm or more and 30 μm or less.

[0144] [negative electrode] The negative electrode includes a negative electrode active material layer and a negative electrode current collector. In addition, the negative electrode active material layer contains a negative electrode active material and may further include a conductive auxiliary agent and a binder.

[0145] <Negative Electrode Active Material> As the negative electrode active material, for example, an alloy material and / or a carbon material can be used.

[0146] As the carbon material used as the negative electrode active material, one or more selected from graphite, easily graphitizable carbon (soft carbon), hardly graphitizable carbon (hard carbon), carbon fiber (carbon nanotube), graphene, carbon black, etc. can be used.

[0147] As graphite, artificial graphite or natural graphite can be cited. As artificial graphite, for example, mesocarbon microbeads (MCMB), coke-based artificial graphite, pitch-based artificial graphite, etc. can be cited. Here, spherical graphite with a spherical shape can be used as artificial graphite. For example, MCMB sometimes has a spherical shape, so it is preferred. In addition, MCMB is relatively easy to reduce its surface area, so it is sometimes preferred. As natural graphite, for example, flaky graphite, spheroidized natural graphite, etc. can be cited.

[0148] When lithium ions are intercalated in graphite (when lithium-graphite intercalation compounds are generated), graphite shows a potential as low as that of lithium metal (0.05 V or more and 0.3 V or less vs. Li + / Li). As a result, lithium-ion batteries using graphite can show high operating voltages. Graphite also has the following advantages: large capacity per unit volume; small volume expansion; relatively cheap; and higher safety than lithium metal, so it is preferred.

[0149] As the negative electrode active material, an element that can react to charge and discharge by alloying / dealloying with lithium can be used. For example, a material containing one or more of silicon, tin, gallium, aluminum, germanium, lead, antimony, bismuth, silver, zinc, cadmium and indium can be used. The capacity of this element is higher than that of carbon, especially the theoretical capacity of silicon is high, which is 4200mAh / g. In addition, compounds containing these elements can also be used. For example, SiO, Mg2Si, Mg2Ge, SnO, SnO2, Mg2Sn, SnS2, V2Sn3, FeSn2, CoSn2, Ni3Sn2, Cu6Sn5, Ag3Sn, Ag3Sb, Ni2MnSb, CeSb3, LaSn3, La3Co2Sn7, CoSb3, InSb and SbSn can be cited. Here, elements that can react to charge and discharge by alloying / dealloying with lithium and compounds containing the elements are sometimes referred to as alloy materials.

[0150] In this specification, "SiO" refers to silicon monoxide, for example. Alternatively, SiO may also be represented as SiO xHere, x preferably represents a value of 1 or a value close to 1. For example, x is preferably 0.2 or more and 1.5 or less, and more preferably 0.3 or more and 1.2 or less.

[0151] In addition, as the negative electrode active material, titanium dioxide (TiO2), lithium titanium oxide (Li4Ti5O 12 ), lithium-graphite intercalation compound (Li x C6), niobium pentoxide (Nb2O5), tungsten dioxide (WO2), molybdenum dioxide (MoO2), etc., one or more oxides thereof.

[0152] In addition, as the negative electrode active material, Li 3N type structure containing lithium and transition metal nitride can be used. 3-x M x N (M = Co, Ni, Cu). For example, Li 2.6 Co 0.4 N3 shows a large charge and discharge capacity (900 mAh / g, 1890 mAh / cm 3 ), so it is preferred.

[0153] When a nitride containing lithium and a transition metal is used, lithium ions are contained in the negative electrode active material, so it can be combined with a material that does not contain lithium ions, such as V2O5 and Cr3O8, which is used as a positive electrode active material, and is therefore preferred. Note that when a material containing lithium ions is used as a positive electrode active material, a nitride containing lithium and a transition metal can also be used as a negative electrode active material by previously removing the lithium ions contained in the positive electrode active material.

[0154] In addition, materials that cause conversion reactions can also be used as negative electrode active materials. For example, transition metal oxides that do not form alloys with lithium, such as cobalt oxide (CoO), nickel oxide (NiO), and iron oxide (FeO), can be used as negative electrode active materials. Materials that cause conversion reactions can also include oxides such as Fe2O3, CuO, Cu2O, RuO2, and Cr2O3, CoS 0.89 , sulfides such as NiS, CuS, nitrides such as Zn3N2, Cu3N, Ge3N4, phosphides such as NiP2, FeP2, CoP3, fluorides such as FeF3, BiF3.

[0155] In addition, a plurality of the above-mentioned negative electrode active materials may be combined. For example, a negative electrode active material of mixed graphite and silicon particles may be used. Silicon particles refer to silicon powder, which is a material for the negative electrode active material of a lithium-ion secondary battery. The average particle size of its particle size distribution, that is, the average particle size is around 100 nm, and is sometimes referred to as nano silicon particles. As the silicon particles used, it is preferred that the silicon raw material is crushed and adjusted to a uniform particle size. The silicon particles may also contain at least one of silicon, silicon oxide, and silicon alloy. Note that the particle size can typically be measured using laser diffraction particle size distribution measurement, but is not limited to laser diffraction particle size distribution measurement, and the major axis of the particle cross section may also be measured by analysis using SEM (Scanning Electron Microscopy) or TEM.

[0156] As the conductive aid and binder that may be contained in the negative electrode active material layer, the same materials as those that may be contained in the positive electrode active material layer can be used.

[0157] <Negative Electrode Current Collector> As the negative electrode current collector, copper or the like may be used in addition to the same materials as the positive electrode current collector. In addition, as the negative electrode current collector, it is preferable to use a material that does not alloy with carrier ions such as lithium.

[0158] [Electrolyte] The electrolyte solution contains an organic solvent, but the organic solvent is not limited to being liquid at 25°C, and may be solid at 25°C, or may be semi-solid at room temperature. Note that the organic solvent is preferably liquid in a wide temperature range including below freezing point to high temperature, but is not limited thereto. The organic solvent may be liquid, solid, or semi-solid in a wide temperature range including below freezing point to high temperature.

[0159] As the organic solvent, an aprotic organic solvent is preferably used, for example, one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate, vinyl chloride carbonate, vinylene carbonate, γ-butyrolactone, γ-valerolactone, dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), 1,3-propane sultone (PS), fluoroethylene carbonate (FEC), methyl 3,3,3-trifluoropropionate (MTFP), methyl formate, methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, 1,3-dioxane, 1,4-dioxane, ethylene glycol dimethyl ether (DME), dimethyl sulfoxide, diethyl ether, methyl diglyme, acetonitrile, benzonitrile, tetrahydrofuran, sulfolane, sultone, etc. can be used, or two or more of the above can be used in any combination and ratio.

[0160] Because PS has the same HOMO (Highest Occupied Molecular Orbital: highest occupied molecular orbital) energy level and LUMO (Lowest Unoccupied Molecular Orbital: lowest unoccupied molecular orbital) energy level as EC and DEC, it is not easily oxidized and reduced even at a high cutoff voltage, and it is easy to become a polymer when it is decomposed on the surface of the positive electrode active material. Therefore, it has the advantage of not easily becoming a decomposition product with a small molecular weight and gasifying. Therefore, the electrolyte preferably contains PS at 0.1wt% or more and 10wt% or less, and more preferably contains PS at 0.25wt% or more and 7.5wt% or less.

[0161] FEC is one of the cyclic carbonates, and because it has a high relative dielectric constant, it has the effect of promoting the dissociation of lithium salts when used in organic solvents. On the other hand, since FEC has an electron-withdrawing substituent, it is easier to generate and desolvate lithium ions than EC. Specifically, the solvation energy of lithium ions in FEC is smaller than that of EC without an electron-withdrawing substituent. Therefore, lithium ions are easy to leave the surface of the positive electrode active material and the surface of the negative electrode active material, thereby reducing the internal resistance of the secondary battery. Furthermore, the HOMO energy level of FEC is deep, so it is not easy to oxidize and the oxidation resistance is improved. On the other hand, there is a concern about the high viscosity of FEC. Therefore, it is preferred to use a mixed organic solvent containing MTFP in addition to FEC for the electrolyte. MTFP is one of the chain carbonates, which can produce the effect of reducing the viscosity of the electrolyte or maintaining the viscosity at room temperature (typically 25°C) at low temperatures (typically 0°C). In addition, the solvation energy of MTFP is smaller than that of methyl propionate (abbreviated as "MP") which does not have an electron-withdrawing substituent, so it can sometimes be solvated with lithium ions when used in an electrolyte. When a mixed organic solvent containing both FEC and MTFP is used, when the volume ratio is FEC:MTFP=1:y, preferably 2≤y≤20, more preferably 4≤y≤9.

[0162] Preferably, the content of particulate dust in the organic solvent or molecules other than the constituent molecules of the organic solvent (hereinafter referred to as "impurities", including oxygen (O2), water (H2O) or moisture) is small and highly purified. In addition, it is preferred that the reaction by-products during the appropriate purification synthesis are suppressed. Specifically, the impurity concentration of the electrolyte is less than 100 ppm, preferably less than 50 ppm, and more preferably less than 10 ppm. The concentration of water in the impurities can be detected by Karl Fischer titration.

[0163] Furthermore, the organic solvent is preferably such that the peaks caused by impurities are hardly confirmed by NMR measurement or the like. Hardly confirmed means that the ratio of the integrated area of ​​the peaks caused by impurities to the integrated area of ​​the peaks caused by the main component (abbreviated as the integrated ratio) is 0.005 or less, preferably 0.002 or less. There is no particular limitation on the device used for NMR measurement, for example, the "AVANCE III 400" manufactured by Bruker can be used. In addition, the central peak of the five peaks of acetonitrile derived from acetonitrile-d3 used for solvent in 1H-NMR measurement can be set to 1.94ppm.

[0164] For example, it is known that: in the case of using MTFP, when 1H-NMR is measured using acetonitrile-d3 solvent, four peaks are generated in the range of δ being more than 3.29ppm and less than 3.43ppm. However, when other peaks are also generated in the vicinity thereof, for example, when a peak appears in the range of δ being more than 3.24ppm and less than 3.29ppm, it can be considered that the peak originates from impurities. Therefore, when the ratio (integral ratio) of the peak area of ​​more than 3.24ppm and less than 3.29ppm relative to the peak area of ​​more than 3.29ppm and less than 3.43ppm is less than 0.005, preferably less than 0.002, it can be said that the peak caused by impurities is almost not confirmed.

[0165] In addition, by using one or more ionic liquids (room temperature molten salts) with flame retardancy and low volatility as solvents for the electrolyte, even if the internal temperature rises due to internal short circuit or overcharge of the storage device, the rupture and ignition of the storage device can be prevented. The ionic liquid is composed of cations and anions, including organic cations and anions. As organic cations for the electrolyte, aliphatic onium cations such as quaternary ammonium cations, tertiary sulfonium cations and quaternary phosphonium cations or aromatic cations such as imidazolium cations and pyridinium cations can be cited. In addition, as anions for the electrolyte, monovalent amide anions, monovalent methylated anions, fluorosulfonic acid anions, perfluoroalkyl sulfonic acid anions, tetrafluoroborate anions, perfluoroalkyl borate anions, hexafluorophosphate anions or perfluoroalkyl phosphate anions can be cited.

[0166] In addition, as the electrolyte dissolved in the above solvent, for example, LiPF6, LiClO4, LiAsF6, LiBF4, LiAlCl4, LiSCN, LiBr, LiI, Li2SO4, Li2B 10 Cl 10 、Li2B 12 Cl 12 , LiCF3SO3, LiC4F9SO3, LiC(CF3SO2)3, LiC(C2F5SO2)3, LiN(CF3SO2)2, LiN(C4F9SO2) One of the lithium salts such as (CF3SO2), LiN(C2F5SO2)2, lithium bis(oxalatoborate) (Li(C2O4)2, LiBOB), etc., or two or more of the above can be used in any combination and proportion.

[0167] As an electrolyte for a power storage device, it is preferred to use a highly purified electrolyte with a low content of granular dust or elements other than the constituent elements of the electrolyte (hereinafter referred to as "impurities"). Specifically, the proportion of impurities in the weight of the electrolyte is preferably less than 1%, more preferably less than 0.1%, and further preferably less than 0.01%.

[0168] Alternatively, a polymer gel electrolyte in which a polymer is swollen with an electrolyte solution may be used.

[0169] Furthermore, by using a polymer gel electrolyte, safety against leakage etc. is improved, and the secondary battery can be made thinner and lighter.

[0170] As the polymer of gelation, silicone gel, acrylic acid glue, acrylonitrile gel, polyethylene oxide gel, polypropylene oxide gel, fluorine polymer gel etc. can be used.For example, the polymer with polyoxyalkylene structure such as polyethylene oxide (PEO), PVDF and polyacrylonitrile etc. and the copolymers comprising these etc. can be used.For example, PVDF-HFP as the copolymer of PVDF and hexafluoropropylene (HFP) can be used.In addition, the formed polymer can also have a porous shape.

[0171] In addition, as an alternative to the electrolyte, a solid electrolyte containing an inorganic material such as a sulfide or an oxide or a solid electrolyte containing a polymer material such as a PEO (polyethylene oxide) can be used. When a solid electrolyte is used, there is no need to set a separator or a spacer. In addition, since the entire battery can be solidified, there is no worry about leakage and safety is significantly improved.

[0172] [Isolated Body] When the electrolyte includes a liquid electrolyte, a separator is arranged between the positive electrode and the negative electrode. As a separator, for example, the following materials can be used: materials formed by fibers having cellulose such as paper, non-woven fabrics, glass fibers, ceramics, or synthetic fibers using nylon (polyamide), vinylon (polyvinyl alcohol fibers), polypropylene (denoted as PP), polyimide (denoted as PI), polyester, acrylic resin, polyolefin, polyurethane, etc. The porosity of the thickness of the separator can be greater than 35% and less than 90%, preferably greater than 60% and less than 85%. The porosity of the separator using polypropylene can be greater than 35% and less than 45%. The porosity of the separator using polyimide can be greater than 75% and less than 85%. The thickness of the separator is preferably greater than 10μm and less than 80μm, more preferably greater than 20μm and less than 60μm. The separator using polyimide can have a high porosity and can achieve thick film (typically, the thickness is greater than 50μm and less than 60μm), so it is preferred.

[0173] The separator is preferably processed into a bag shape and arranged so as to surround either the positive electrode or the negative electrode.

[0174] The separator may have a multilayer structure. For example, a ceramic material, a fluorine material, a polyamide material or a mixture thereof may be coated on a thin film of an organic material such as polypropylene or polyethylene. As a ceramic material, for example, aluminum oxide particles or silicon oxide particles may be used. As a fluorine material, for example, PVDF or polytetrafluoroethylene may be used. As a polyamide material, for example, nylon or aromatic polyamide (meta-aramid or para-aramid) may be used.

[0175] By adopting a separator with a multilayer structure, the safety of the lithium ion battery can be ensured even if the total thickness of the separator is small, and thus the capacity per unit volume of the lithium ion battery can be increased.

[0176] [Outer packaging] As the outer packaging body included in the lithium ion battery, for example, a metal material such as aluminum or a resin material can be used. In addition, a film-shaped outer packaging body can also be used. As the film, for example, a three-layer film can be used: a metal film with excellent flexibility such as aluminum, stainless steel, copper, nickel, etc. is arranged on a film composed of materials such as polyethylene, polypropylene, polycarbonate, ionomer, polyamide, etc., and an insulating synthetic resin film such as polyamide resin, polyester resin, etc. is arranged on the metal film as the outer surface of the outer packaging body.

[0177] This embodiment mode can be used in combination with other embodiment modes.

[0178] Implementation 3 In this embodiment, an example of one form of a lithium ion battery is described.

[0179] [Laminated lithium-ion battery] Fig.14A and Fig. 14B An example of one embodiment of a laminated lithium ion battery 500 is shown. Fig.14A and Fig. 14B is an appearance diagram, the lithium ion battery 500 includes the electrolyte and separator ( Fig.14A and Fig. 14B ), a negative electrode 506 and a positive electrode 507. In the lithium ion battery 500, the negative electrode 506 preferably has a larger area than the positive electrode 507. Furthermore, the lithium ion battery 500 includes a negative electrode lead electrode 510 electrically connected to the negative electrode 506 and a positive electrode lead electrode 511 electrically connected to the positive electrode 507. The electrolyte, the negative electrode 506 and the positive electrode 507 are contained in an outer package 509, and a part of the negative electrode lead electrode 510 and a part of the positive electrode lead electrode 511 protrude from the outer package 509. A bonding area 508 is provided at a part of the outer periphery of the outer package 509. Fig.14A An example of a mode in which the negative lead electrode 510 and the positive lead electrode 511 protrude from the same side of the outer package 509 is shown, and the bonding area 508 is located at least on the side where each lead electrode protrudes and two sides adjacent to the side. Fig. 14B The example of a mode in which the side of the negative lead electrode 510 protruding from the outer package 509 and the side of the positive lead electrode 511 protruding from the outer package 509 are opposite to each other is shown, and the bonding area 508 is located at least on the two sides protruding from each lead electrode and one side sandwiched between the two sides. Fig.14A and Fig. 14B In the embodiment, the side where the adhesive region 508 is not provided preferably corresponds to the side where the outer packaging body 509 is folded.

[0180] When the positive electrode active material of the present invention is used in the laminated lithium ion battery 500, a secondary battery having a high capacity, a high discharge capacity and good cycle characteristics can be realized.

[0181] [Coin-type lithium-ion battery] An example of a coin-type lithium-ion battery will be described. Fig.15A This is an exploded perspective view of a coin-type (single-layer flat) lithium-ion battery. Fig. 15B This is its appearance picture. Fig. 15C Coin-type lithium-ion batteries are mainly used in small electronic devices. In this specification, etc., coin-type lithium-ion batteries include button-type lithium-ion batteries.

[0182] In order to easily understand the overlapping relationship (upper and lower relationship and position relationship) of components, Fig.15A A schematic diagram is used. Therefore, Fig.15A Not with Fig. 15B Exactly the same picture.

[0183] exist Fig.15A In the embodiment, the positive electrode 304, the negative electrode 307, the spacer 342 and the gasket 332 are overlapped, and the negative electrode can 302 and the positive electrode can 301 are used to seal the above components. Fig.15A The electrolyte and separator described in the above embodiment are not shown. The spacer 342 and the gasket 332 are used to protect the inside or fix the position in the tank when the positive electrode tank 301 and the negative electrode tank 302 are pressed together. The spacer 342 and the gasket 332 are made of stainless steel or an insulating material.

[0184] A stacked structure in which a positive electrode active material layer 306 is formed on a positive electrode current collector 305 is referred to as a positive electrode 304 .

[0185] Fig. 15B It is a perspective view of the manufactured coin-type lithium-ion battery 300 .

[0186] In the coin-type lithium-ion battery 300, the positive electrode can 301 also serving as the positive terminal and the negative electrode can 302 also serving as the negative terminal may be insulated and sealed by a gasket 303 formed of polypropylene or the like. The positive electrode 304 is formed of a positive electrode current collector 305 and a positive electrode active material layer 306 provided in contact with the positive electrode. In addition, the negative electrode 307 is formed of a negative electrode current collector 308 and a negative electrode active material layer 309 provided in contact with the negative electrode. The positive electrode can 301 is electrically connected to the positive electrode 304, and the negative electrode can 302 is electrically connected to the negative electrode 307.

[0187] In the positive electrode 304 and the negative electrode 307 used in the coin-type lithium ion battery 300 , the active material layer may be formed on one surface respectively.

[0188] like Fig. 15C As shown, the positive electrode can 301 is placed at the bottom, the positive electrode 304, the negative electrode 307 and the negative electrode can 302 are stacked in order, and the positive electrode can 301 and the negative electrode can 302 are press-fitted with the gasket 303 interposed therebetween to manufacture the coin-type lithium ion battery 300.

[0189] When the positive electrode active material of the present invention is used in the coin-type lithium ion battery 300, a secondary battery having high capacity, high discharge capacity, and good cycle characteristics can be realized.

[0190] [Cylindrical lithium-ion battery] Reference Fig.16A The following describes an example of a cylindrical lithium-ion battery. Fig.16A As shown, the top surface of the cylindrical lithium ion battery 616 includes a positive electrode cover (battery cover) 601, and the side and bottom surfaces thereof include a battery can (outer can) 602. The positive electrode cover 601 and the battery can (outer can) 602 are insulated by a gasket (insulating gasket) 610.

[0191] Fig. 16B It is a diagram schematically showing a cross section of a cylindrical lithium ion battery. Fig. 16B The cylindrical lithium ion battery shown has a positive electrode cover (battery cover) 601 on the top surface and a battery can (outer can) 602 on the side and bottom surfaces. The positive electrode cover and the battery can (outer can) 602 are insulated by a gasket (insulating gasket) 610.

[0192] A battery element is provided inside the hollow cylindrical battery can 602, in which a strip-shaped positive electrode 604 and a strip-shaped negative electrode 606 are wound with an electrolyte layer 605 sandwiched therebetween. Although not shown in the figure, the battery element is wound around the central axis. One end of the battery can 602 is closed and the other end is open. Inside the battery can 602, the battery element in which the positive electrode, the negative electrode, and the separator are wound is sandwiched by a pair of opposing insulating plates 608 and insulating plates 609. In addition, an electrolyte (not shown) is injected into the interior of the battery can 602 in which the battery element is provided.

[0193] Since the positive electrode and negative electrode used in the cylindrical storage battery are wound, it is preferable that the active material is formed on both sides of the current collector. FIG. 16A to FIG. 16D The lithium ion battery 616 is shown in which the height of the cylinder is greater than the diameter of the cylinder, but the present invention is not limited thereto. Alternatively, a lithium ion battery in which the diameter of the cylinder is greater than the height of the cylinder may be used. By adopting the above structure, for example, the lithium ion battery can be miniaturized.

[0194] The positive electrode 604 is connected to the positive terminal (positive electrode current collecting wire) 603, and the negative electrode 606 is connected to the negative terminal (negative electrode current collecting wire) 607. Metal materials such as aluminum can be used for both the positive terminal 603 and the negative terminal 607. The positive terminal 603 is resistance-welded to the safety valve mechanism 613, and the negative terminal 607 is resistance-welded to the bottom of the battery can 602. The safety valve mechanism 613 is electrically connected to the positive electrode cover 601 through a PTC element (Positive Temperature Coefficient) 611. When the internal pressure of the battery rises to exceed a specified threshold, the safety valve mechanism 613 cuts off the electrical connection between the positive electrode cover 601 and the positive electrode 604. In addition, the PTC element 611 is a thermally sensitive resistance element whose resistance increases when the temperature rises, and limits the current by increasing the resistance to prevent abnormal heating. As the PTC element 611, a barium titanate (BaTiO3)-based ceramic material or the like can be used.

[0195] Fig. 16CAn example of a power storage system 615 is shown. The power storage system 615 includes a plurality of lithium ion batteries 616, which is sometimes referred to as a battery pack. The positive electrode of each lithium ion battery contacts a conductor 624 separated by an insulator 625, and the positive electrodes are electrically connected to each other. The conductor 624 is electrically connected to a control circuit 620 via a wiring 623. In addition, the negative electrode of each lithium ion battery is electrically connected to the control circuit 620 via a wiring 626. As the control circuit 620, a protection circuit for preventing overcharge or overdischarge or the like can be used.

[0196] Fig.16D An example of a power storage system 615 is shown. The power storage system 615 includes a plurality of lithium-ion batteries 616, and the plurality of lithium-ion batteries 616 are sandwiched between a conductive plate 628 and a conductive plate 614. The plurality of lithium-ion batteries 616 are electrically connected to the conductive plate 628 and the conductive plate 614 through a wiring 627. The plurality of lithium-ion batteries 616 can be connected in parallel, connected in series, or connected in parallel and then in series. By configuring the power storage system 615 including the plurality of lithium-ion batteries 616, a large amount of electric power can be obtained.

[0197] A plurality of lithium-ion batteries 616 may be connected in parallel and then in series.

[0198] In addition, a temperature control device may be included between the plurality of lithium-ion batteries 616. When the lithium-ion battery 616 is overheated, it can be cooled by the temperature control device, and when the lithium-ion battery 616 is overcooled, it can be heated by the temperature control device. Therefore, the performance of the power storage system 615 is not easily affected by the external temperature.

[0199] In addition, Fig.16D In FIG. 6 , the power storage system 615 is electrically connected to the control circuit 620 via wiring 621 and wiring 622. The wiring 621 is electrically connected to the positive electrodes of the plurality of lithium ion batteries 616 via the conductive plate 628, and the wiring 622 is electrically connected to the negative electrodes of the plurality of lithium ion batteries 616 via the conductive plate 614.

[0200] When the positive electrode active material of the present invention is used for the cylindrical lithium ion battery 616, a secondary battery having a high capacity, a high discharge capacity and good cycle characteristics can be realized.

[0201] [Other structural examples of lithium-ion batteries] use FIG. 17A to FIG. 18C An example of the structure of a lithium-ion battery is described.

[0202] Fig.17AThe lithium ion battery 913 shown includes a winding body 950 provided with a terminal 951 and a terminal 952 inside a frame 930. The winding body 950 is impregnated with an electrolyte inside the frame 930. The terminal 952 is in contact with the frame 930, and the terminal 951 is prevented from contacting the frame 930 by an insulating material. Note that for convenience, although Fig.17A Frame 930 is shown separately in the figure, but in reality, winding body 950 is covered by frame 930, and terminals 951 and 952 extend outside frame 930. Frame 930 can be made of a metal material (such as aluminum) or a resin material.

[0203] In addition, if Fig. 17B As shown, multiple materials can also be used to form Fig.17A For example, in the frame 930 shown in FIG. Fig. 17B In the illustrated lithium ion battery 913 , a frame body 930 a and a frame body 930 b are bonded together, and a wound body 950 is provided in a region surrounded by the frame bodies 930 a and 930 b .

[0204] As the frame 930a, an insulating material such as an organic resin can be used. In particular, by using a material such as an organic resin to form the surface of the antenna, it is possible to suppress the shielding of the electric field by the lithium ion battery 913. In addition, if the electric field shielding caused by the frame 930a is small, the antenna can be provided inside the frame 930a. As the frame 930b, for example, a metal material can be used.

[0205] Furthermore, Fig. 17C 9 shows the structure of the wound body 950. The wound body 950 includes a negative electrode 931, a positive electrode 932, and an electrolyte layer 933. The wound body 950 is formed by overlapping the negative electrode 931 and the positive electrode 932 with the electrolyte layer 933 interposed therebetween to form a laminated sheet, and then winding the laminated sheet. In addition, a plurality of layers of the negative electrode 931, the positive electrode 932, and the electrolyte layer 933 may be stacked.

[0206] Alternatively, you can use 18A to 18C A lithium-ion battery 913 including a jellyroll 950a is shown. Fig.18A The wound body 950a shown includes a negative electrode 931, a positive electrode 932, and an electrolyte layer 933. The negative electrode 931 includes a negative electrode active material layer 931a. The positive electrode 932 includes a positive electrode active material layer 932a.

[0207] The width of the electrolyte layer 933 is greater than that of the negative electrode active material layer 931a and the positive electrode active material layer 932a, and the electrolyte layer 933 is wound so as to overlap with the negative electrode active material layer 931a and the positive electrode active material layer 932a. In addition, from the viewpoint of safety, it is preferable that the width of the negative electrode active material layer 931a is greater than that of the positive electrode active material layer 932a. In addition, the winding body 950a of the above shape is good in safety and productivity, so it is preferred.

[0208] like Fig.18B As shown, the negative electrode 931 is electrically connected to the terminal 951. The terminal 951 is electrically connected to the terminal 911a. In addition, the positive electrode 932 is electrically connected to the terminal 952. The terminal 952 is electrically connected to the terminal 911b.

[0209] like Fig.18C As shown, the wound body 950a is covered by the frame 930 to form a lithium ion battery 913. The frame 930 is preferably provided with a safety valve, an overcurrent protection element, etc. The safety valve is a valve that is opened at a specified internal pressure in the frame 930 to prevent battery rupture.

[0210] like Fig.18B As shown, the lithium-ion battery 913 may also include a plurality of winding bodies 950a. By using a plurality of winding bodies 950a, a lithium-ion battery 913 with a larger charge and discharge capacity can be realized. Fig.18A and Fig.18B The other components of the lithium-ion battery 913 shown can be referred to FIG. 17A to FIG. 17C The lithium ion battery 913 is shown.

[0211] When the positive electrode active material of the present invention is used for the lithium ion battery 913 including the wound body, a secondary battery having a high capacity, a high discharge capacity, and good cycle characteristics can be realized.

[0212] The content of this embodiment mode can be combined with the content of other embodiment modes as appropriate.

[0213] Implementation 4 In this embodiment, using Fig.19A and Fig.19B An example applicable to electric vehicles (EV) is described below.

[0214] like Fig.19A As shown, in an electric vehicle, first batteries 1301a and 1301b are provided as lithium-ion batteries for main driving, and a second battery 1311 is provided to supply power to an inverter 1312 for starting an engine 1304. When the positive electrode active material of one embodiment of the present invention is used for the first batteries 1301a and 1301b, a secondary battery having a high capacity, a high discharge capacity, and good cycle characteristics can be realized.

[0215] The second battery 1311 is also called a cranking battery (also called a starting battery). The second battery 1311 only needs to have a high output and does not necessarily need to have a high capacity. In addition, the capacity of the second battery 1311 is smaller than that of the first batteries 1301a and 1301b.

[0216] The internal structure of the first battery 1301a may be either a winding type or a stacked type. In addition, the first battery 1301a may also use the secondary battery of the above embodiment. By using the secondary battery of the above embodiment as the first battery 1301a, a high capacity can be achieved, safety is improved, and miniaturization and lightness can be achieved.

[0217] In this embodiment, an example of connecting the first batteries 1301a and 1301b in parallel is shown, but more than three batteries may be connected in parallel. In addition, as long as sufficient power can be stored in the first battery 1301a, the first battery 1301b may not be provided. By forming a battery pack with a plurality of lithium-ion batteries, a large amount of power can be taken out. A plurality of lithium-ion batteries may be connected in parallel, in series, or in series after being connected in parallel. Sometimes a plurality of lithium-ion batteries are referred to as a battery pack.

[0218] In order to cut off the power from the plurality of lithium-ion batteries, the vehicle-mounted lithium-ion battery includes a charging plug or a circuit breaker that can cut off the high voltage without using a tool, which is provided in the first battery 1301a.

[0219] In addition, the power of the first battery 1301a, 1301b is mainly used to rotate the engine 1304, and also supplies power to the 42V system vehicle components (electric power steering system 1307, heater 1308, defogger 1309, etc.) through the DCDC circuit 1306. In the case where the rear wheels include a rear engine 1317, the first battery 1301a is used to rotate the rear engine 1317.

[0220] Furthermore, the second battery 1311 supplies power to 14V system vehicle-mounted components (audio 1313 , power windows 1314 , lights 1315 , etc.) via the DCDC circuit 1310 .

[0221] In addition, use Fig.19B The first battery 1301a is described.

[0222] Fig.19BAn example of using nine rectangular lithium-ion batteries 1300 as a battery pack 1415 is shown. In addition, the nine rectangular lithium-ion batteries 1300 are connected in series and one electrode is fixed using a fixing portion 1413 formed of an insulator and the other electrode is fixed using a fixing portion 1414 formed of an insulator. In this embodiment, an example of fixing using fixing portions 1413 and 1414 is shown, but it can also be stored in a battery storage box (also referred to as a frame). Assuming that the vehicle is subjected to vibration or shaking from the outside (road surface, etc.), it is preferable to use fixing portions 1413, 1414 and a battery storage box to fix multiple lithium-ion batteries. In addition, one electrode is electrically connected to the control circuit unit 1320 via wiring 1421. The other electrode is electrically connected to the control circuit unit 1320 via wiring 1422.

[0223] Alternatively, a memory circuit including a transistor using an oxide semiconductor may be used as the control circuit portion 1320. A charge control circuit or a battery control system including a memory circuit including a transistor using an oxide semiconductor is sometimes referred to as a BTOS (Battery operating system or Battery oxide semiconductor).

[0224] It is preferred to use a metal oxide used as an oxide semiconductor. For example, as an oxide, it is preferred to use a metal oxide such as In-M-Zn oxide (element M is selected from one or more of aluminum, gallium, yttrium, copper, vanadium, beryllium, boron, titanium, iron, nickel, germanium, zirconium, molybdenum, lanthanum, cerium, neodymium, hafnium, tantalum, tungsten and magnesium). In particular, the In-M-Zn oxide that can be applied to the oxide is preferably CAAC-OS (C-Axis Aligned Crystal Oxide Semiconductor) or CAC-OS (Cloud-Aligned Composite Oxide Semiconductor). In addition, In-Ga oxide and In-Zn oxide can also be used as oxides. CAAC-OS is an oxide semiconductor including a plurality of crystalline regions, and the c-axis of the plurality of crystalline regions is oriented in a specific direction. In addition, the specific direction refers to the thickness direction of the CAAC-OS film, the normal direction of the formed surface of the CAAC-OS film, or the normal direction of the surface of the CAAC-OS film. In addition, the crystalline region is a region having a periodicity of atomic arrangement. Note that when the atomic arrangement is regarded as a lattice arrangement, the crystalline region is also a region with a consistent lattice arrangement. Furthermore, CAAC-OS has a region where multiple crystalline regions are connected in the ab plane direction, and sometimes the region has distortion. In addition, distortion refers to a portion where the direction of the lattice arrangement changes between a region with a consistent lattice arrangement and other regions with a consistent lattice arrangement in a region where multiple crystalline regions are connected. In other words, CAAC-OS refers to an oxide semiconductor with a c-axis orientation and no obvious orientation in the ab plane direction.

[0225] In addition, the control circuit unit 1320 preferably uses a transistor containing an oxide semiconductor because the transistor can be used in a low temperature environment. In order to simplify the process, the control circuit unit 1320 can also be formed using a unipolar transistor. The operating ambient temperature range of the transistor containing an oxide semiconductor in the semiconductor layer is larger than that of the single-crystalline Si transistor, that is, above -40°C and below 150°C, and the characteristic change of the lithium-ion battery when heated is smaller than that of the single-crystalline Si transistor. The off-state current of the transistor containing an oxide semiconductor is independent of the temperature and is also below the measurement lower limit at 150°C, but the temperature dependence of the off-state current characteristics of the single-crystalline Si transistor is large. For example, at 150°C, the off-state current of the single-crystalline Si transistor increases, and the current switching ratio does not become sufficiently large. The control circuit unit 1320 can improve safety.

[0226] The control circuit unit 1320 using a storage circuit including a transistor using an oxide semiconductor can also be used as an automatic control device for lithium-ion batteries for the causes of instability caused by 10 conditions such as micro-short circuits. As functions for solving the causes of instability caused by the 10 conditions, there can be cited prevention of overcharging, prevention of overcurrent, control of overheating during charging, cell balancing in a battery pack, prevention of overdischarge, a capacity meter, automatic control of charging voltage and current according to temperature, control of charging current according to the degree of degradation, detection of abnormal behavior of micro-short circuits, prediction of abnormalities regarding micro-short circuits, etc. The control circuit unit 1320 has at least one of the above functions. In addition, ultra-miniaturization of the automatic control device for lithium-ion batteries can be achieved.

[0227] In addition, micro short circuit refers to a very small short circuit inside a lithium-ion battery. One of the reasons for micro short circuit is believed to be that multiple charge and discharge cycles cause uneven distribution of the positive electrode active material, local current concentration occurs in part of the positive electrode and part of the negative electrode, or side reactions produce side reaction products, leading to micro short circuit.

[0228] In addition to micro short circuits, the control circuit unit 1320 detects the terminal voltage of the lithium-ion battery and manages the charging and discharging state of the lithium-ion battery. For example, to prevent overcharging, both the output transistor of the charging circuit and the blocking switch can be turned off at almost the same time.

[0229] in addition, Fig.19C Show Fig.19B An example of a block diagram of a battery pack 1415 is shown.

[0230] The control circuit unit 1320 includes: a switch unit 1324 including at least a switch for preventing overcharging and a switch for preventing overdischarging; a control circuit 1322 for controlling the switch unit 1324; and a voltage measuring unit for the first battery 1301a. In the control circuit unit 1320, the upper limit voltage and the lower limit voltage of the lithium ion battery used are set to control the upper limit of the current flowing from the outside and the upper limit of the output current flowing to the outside. The range above the lower limit voltage and below the upper limit voltage of the lithium ion battery is the recommended voltage range. When the voltage is outside this range, the switch unit 1324 functions and serves as a protection circuit. In addition, the control circuit unit 1320 controls the switch unit 1324 to prevent overdischarge and overcharge, so it can also be called a protection circuit. For example, when the control circuit 1322 detects a voltage that will become overcharge, the current is shielded by closing the switch of the switch unit 1324. In addition, the function of shielding the current according to the increase in temperature can also be set by setting a PTC element in the charge and discharge path. In addition, the control circuit unit 1320 includes an external terminal 1325 (+IN) and an external terminal 1326 (−IN).

[0231] The switch portion 1324 may be formed by combining an n-channel transistor and a p-channel transistor. In addition to switches including Si transistors using single crystal silicon, for example, Ge (germanium), SiGe (silicon germanium), GaAs (gallium arsenide), GaAlAs (gallium aluminum arsenic), InP (indium phosphide), SiC (silicon carbide), ZnSe (zinc selenide), GaN (gallium nitride), GaO x The switch section 1324 is composed of a power transistor such as an OS transistor (gallium oxide; x is a real number greater than 0). In addition, the storage element using the OS transistor can be freely configured by stacking it on a circuit using a Si transistor, so it is easy to achieve integration. By stacking the control circuit section 1320 using the OS transistor on the switch section 1324 for integration, the switch section 1324 and the control circuit section 1320 can be integrated into one chip, so miniaturization can be achieved.

[0232] The first battery 1301a and 1301b mainly supply power to the on-board equipment of the 42V system (high voltage system), while the second battery 1311 supplies power to the on-board equipment of the 14V system (low voltage system). In many cases, the second battery 1311 adopts a lead-acid battery because of cost advantages. Although there is an advantage of no maintenance when a lithium-ion secondary battery is used as the second battery 1311, an abnormality that cannot be distinguished during manufacturing may occur during a long period of use, such as more than three years. In particular, in order to prevent the situation in which the second battery 1311 of the starting inverter cannot work and the engine cannot be started even if the first battery 1301a and 1301b have residual capacity, when the second battery 1311 is a lead-acid battery, power is supplied from the first battery to the second battery to charge in a manner that always maintains a fully charged state.

[0233] This embodiment shows an example of using lithium ion batteries for both the first battery 1301a and the second battery 1311, but a lead acid battery, an all-solid-state battery, or a double-layer capacitor may also be used for the second battery 1311. When the positive electrode active material of one embodiment of the present invention is used for the above-mentioned lithium ion battery, a secondary battery with high capacity, high discharge capacity, and good cycle characteristics can be realized.

[0234] In addition, the regenerative energy caused by the rotation of the tire 1316 is transmitted to the engine 1304 through the transmission 1305, and is charged to the second battery 1311 from the engine controller 1303 and the battery controller 1302 through the control circuit unit 1321. In addition, the first battery 1301a is charged from the battery controller 1302 through the control circuit unit 1320. In addition, the first battery 1301b is charged from the battery controller 1302 through the control circuit unit 1320. In order to efficiently charge the regenerative energy, it is preferred that the first batteries 1301a and 1301b can be charged at a high speed.

[0235] The battery controller 1302 can set the charging voltage and charging current of the first batteries 1301a and 1301b, etc. The battery controller 1302 sets the charging conditions according to the charging characteristics of the lithium-ion battery used to perform high-speed charging.

[0236] In addition, although not shown in the figure, when connected to an external charger, the socket of the charger or the connecting cable of the charger is electrically connected to the battery controller 1302. The power supplied from the external charger is charged to the first battery 1301a, 1301b through the battery controller 1302. In addition, some chargers are provided with a control circuit without using the function of the battery controller 1302, but in order to prevent overcharging, it is preferred to charge the first battery 1301a, 1301b through the control circuit unit 1320. In addition, sometimes the connecting cable or the connecting cable of the charger is provided with a control circuit. The control circuit unit 1320 is sometimes referred to as an ECU (Electronic Control Unit). The ECU is connected to a CAN (Controller Area Network) provided in the electric vehicle. CAN is one of the serial communication standards used as an in-vehicle LAN. In addition, the ECU includes a microcomputer. In addition, the ECU uses a CPU or a GPU.

[0237] As external chargers installed in charging stations, there are 100V outlets, 200V outlets, three-phase 200V and 50kW outlets, etc. In addition, it is also possible to charge by supplying power from an external charging device using a contactless power supply method.

[0238] Next, an example in which a lithium ion battery as one embodiment of the present invention is mounted on a vehicle, typically a transportation vehicle, will be described.

[0239] In addition, lithium-ion batteries can be installed in hybrid vehicles (HV), electric vehicles (EV) or plug-in hybrid vehicles (PHV) and other new generation clean energy vehicles. In addition, lithium-ion batteries can also be installed in agricultural machinery, electric bicycles including electric-assisted bicycles, motorcycles, electric wheelchairs, electric karts, small or large ships, submarines, fixed-wing aircraft and rotary-wing aircraft, rockets, artificial satellites, space probes, planetary probes, spacecraft and other transportation vehicles.

[0240] FIG. 20A to FIG. 20D A transport vehicle using one embodiment of the present invention is shown. Fig. 20A The car 2001 shown is an electric car using an electric motor as a power source for traveling. Alternatively, the car 2001 is a hybrid car that can appropriately select an electric motor and an engine as a power source for traveling. When the lithium-ion battery is installed in the vehicle, the example of the lithium-ion battery shown in the above embodiment can be set in one or more parts. When the positive electrode active material of one embodiment of the present invention is used for a lithium-ion battery installed in a vehicle, a secondary battery with high capacity, high discharge capacity and good cycle characteristics can be realized.

[0241] Fig. 20A The automobile 2001 shown includes a battery pack 2200, which includes a battery module in which a plurality of lithium-ion batteries are connected. In addition, the battery pack 2200 preferably further includes a charge control device electrically connected to the battery module.

[0242] In addition, in the automobile 2001, the lithium-ion battery of the automobile 2001 can be charged by supplying power from an external charging device using a plug-in method and a contactless power supply method. When charging, the charging method and the specifications of the connector can be appropriately performed according to the methods specified by CHAdeMO (a registered trademark in Japan) or the combined charging system "Combined Charging System". As a lithium-ion battery, a charging station set up in a commercial facility or a home power supply can also be used. For example, by supplying power from the outside using plug-in technology, the power storage device installed in the automobile 2001 can be charged. Charging can be performed by converting AC power into DC power using a conversion device such as an ACDC converter.

[0243] In addition, although not shown in the figure, the power receiving device can also be installed in the vehicle and the power can be supplied non-contactly from the power transmission device on the ground for charging. When the non-contact power supply method is used, by assembling the power transmission device in the road or the outer wall, charging can be performed not only when the vehicle is parked but also when it is driving. In addition, the non-contact power supply method can also be used to send and receive power between two vehicles. Furthermore, solar cells can be installed on the outside of the vehicle to charge the lithium-ion battery when it is parked or driving. Such non-contact power supply can be achieved using electromagnetic induction and magnetic field resonance.

[0244] exist Fig. 20B In the diagram, a large transport vehicle 2002 including an electrically controlled engine is shown as an example of a transport vehicle. The battery module of the transport vehicle 2002 is, for example, a battery module having a maximum voltage of 170V, in which four lithium-ion batteries with a nominal voltage of 3.0V or more and 5.0V or less are connected in series. The battery pack 2201 has the same characteristics as the battery pack 2201 except for the number of lithium-ion batteries. Fig.19B Since the functions are the same, the description is omitted. When the positive electrode active material of one embodiment of the present invention is used for the lithium ion battery of the battery pack 2201, a secondary battery with high capacity, high discharge capacity and good cycle characteristics can be realized.

[0245] exist Fig. 20C 2 shows a large transport vehicle 2003 including an electrically controlled engine as an example. The battery module of the transport vehicle 2003 is, for example, a battery module having a maximum voltage of 600V and in which more than 100 lithium-ion batteries with a nominal voltage of 3.0V or more and 5.0V or less are connected in series. In addition, the battery pack 2202 has the same configuration as the battery module except for the number of lithium-ion batteries constituting the battery module. Fig.19B Since the functions are the same, the description thereof is omitted. When the positive electrode active material of one embodiment of the present invention is used in a lithium ion battery included in a battery module, a secondary battery with high capacity, high discharge capacity and good cycle characteristics can be realized.

[0246] exist Fig.20D , an aircraft 2004 equipped with an engine burning fuel is shown as an example. Fig.20D The aircraft 2004 shown includes wheels for taking off and landing, so it can be said that the aircraft 2004 is a part of a transportation vehicle. In the aircraft 2004, multiple lithium-ion batteries are connected to form a battery module and include a battery pack 2203 having a battery module and a charging control device.

[0247] The battery module of the aircraft 2004 has, for example, eight 4V lithium-ion batteries connected in series and having a maximum voltage of 32V. In addition to the number of lithium-ion batteries constituting the battery module of the battery pack 2203, the battery module has the same Fig.19B The functions are the same, so the description is omitted.

[0248] The content of this embodiment mode can be combined with the content of other embodiment modes as appropriate.

[0249] Implementation method 5 In this embodiment, an example in which a lithium ion battery according to one embodiment of the present invention is mounted on a vehicle such as a two-wheeled vehicle or a bicycle is described.

[0250] Fig.21A An example of an electric bicycle using a lithium ion battery according to one embodiment of the present invention is shown. Fig.21A The lithium ion battery of one embodiment of the present invention can be used in the electric bicycle 8700 shown in the figure. The lithium ion battery of one embodiment of the present invention may also include a protection circuit.

[0251] The electric bicycle 8700 includes a power storage device 8702. The power storage device 8702 supplies power to a motor that assists the rider. In addition, the power storage device 8702 is portable. Fig. 21B The power storage device 8702 taken out of the bicycle is shown. The power storage device 8702 has a plurality of lithium ion batteries 8701 of one embodiment of the present invention built therein, and the remaining power can be displayed on the display unit 8703. When the positive electrode active material of one embodiment of the present invention is used for the lithium ion battery 8701, a secondary battery with high capacity, high discharge capacity and good cycle characteristics can be realized.

[0252] In addition, the power storage device 8702 includes a control circuit 8704 capable of controlling the charging of the lithium ion battery or detecting abnormalities. The control circuit 8704 is electrically connected to the positive and negative electrodes of the lithium ion battery 8701. This greatly contributes to reducing accidents such as fires caused by lithium ion batteries.

[0253] Fig. 21C This is an example of a two-wheeled vehicle using the lithium ion battery of one embodiment of the present invention. Fig. 21C The illustrated scooter 8600 includes a power storage device 8602, a side mirror 8601, and a turn signal lamp 8603. The power storage device 8602 can supply power to the turn signal lamp 8603. When the positive electrode active material of one embodiment of the present invention is used for a lithium ion battery, a secondary battery having a high capacity, a high discharge capacity, and good cycle characteristics can be realized.

[0254] exist Fig. 21CIn the illustrated scooter 8600, the power storage device 8602 can be stored in the under-seat storage section 8604. Even if the under-seat storage section 8604 is small, the power storage device 8602 can be stored in the under-seat storage section 8604.

[0255] The content of this embodiment mode can be combined with the content of other embodiment modes as appropriate.

[0256] Implementation 6 In this embodiment, an example of installing a lithium ion battery of one embodiment of the present invention in an electronic device is described. As an electronic device equipped with a lithium ion battery, for example, a television device (also referred to as a television or a television receiver), a display for a computer, a digital camera, a digital video camera, a digital photo frame, a mobile phone (also referred to as a mobile phone, a mobile phone device), a portable game console, a portable information terminal, a sound reproduction device, a large game console such as a pinball machine, etc. can be cited. As a portable information terminal, a notebook personal computer, a tablet terminal, an electronic book terminal, a mobile phone, etc. can be cited.

[0257] Fig.22A An example of a mobile phone is shown. The mobile phone 2100 includes an operation button 2103, an external connection port 2104, a speaker 2105, a microphone 2106, and the like in addition to a display unit 2102 installed in a housing 2101. In addition, the mobile phone 2100 includes a lithium ion battery 2107. When the positive electrode active material of one embodiment of the present invention is used as a lithium ion battery, a secondary battery with high capacity, high discharge capacity, and good cycle characteristics can be realized.

[0258] The mobile phone 2100 can execute various application programs such as mobile phone, e-mail, article reading and writing, music playing, Internet communication, computer games, etc.

[0259] The operation button 2103 may have various functions in addition to time setting, such as power switch, wireless communication switch, silent mode setting and cancellation, power saving mode setting and cancellation, etc. For example, by using the operating system incorporated in the mobile phone 2100, the function of the operation button 2103 can be freely set.

[0260] In addition, the mobile phone 2100 can perform short-range wireless communication standardized by the communication. For example, by communicating with a headset capable of wireless communication, a hands-free call can be made.

[0261] In addition, the mobile phone 2100 has an external connection port 2104, and data can be directly sent to or received from other information terminals through a connector. In addition, charging can also be performed through the external connection port 2104. In addition, the charging operation can also be performed using wireless power supply without using the external connection port 2104.

[0262] The mobile phone 2100 preferably includes a sensor. For example, a fingerprint sensor, a pulse sensor, a human body sensor such as a temperature sensor, a touch sensor, a pressure sensor, an acceleration sensor, etc. are preferably installed as the sensor.

[0263] Fig. 22B An unmanned aerial vehicle 2300 including a plurality of rotors 2302 is shown. The unmanned aerial vehicle 2300 is also referred to as a drone. The unmanned aerial vehicle 2300 includes a lithium ion battery 2301 of one embodiment of the present invention, a camera 2303, and an antenna (not shown). The unmanned aerial vehicle 2300 can be remotely operated via the antenna. When the positive electrode active material of one embodiment of the present invention is used for a lithium ion battery, a secondary battery with high capacity, high discharge capacity, and good cycle characteristics can be realized.

[0264] Fig. 22C An example of a robot is shown. Fig. 22C The robot 6400 shown includes a lithium-ion battery 6409, an illumination sensor 6401, a microphone 6402, an upper camera 6403, a speaker 6404, a display unit 6405, a lower camera 6406, an obstacle sensor 6407, a moving mechanism 6408, a computing device, and the like.

[0265] The microphone 6402 has a function of detecting the user's voice and surrounding sounds, etc. In addition, the speaker 6404 has a function of emitting sound. The robot 6400 can communicate with the user through the microphone 6402 and the speaker 6404.

[0266] The display unit 6405 has the function of displaying various information. The robot 6400 can display the information required by the user on the display unit 6405. The display unit 6405 can also be equipped with a touch panel. In addition, the display unit 6405 can be a detachable information terminal, and by setting it at a fixed position of the robot 6400, it can be charged and send and receive data.

[0267] The upper camera 6403 and the lower camera 6406 have the function of photographing the surrounding environment of the robot 6400. In addition, the obstacle sensor 6407 can detect whether there is an obstacle in the direction of the robot 6400 when it moves forward using the moving mechanism 6408. The robot 6400 can confirm the surrounding environment using the upper camera 6403, the lower camera 6406, and the obstacle sensor 6407 and move safely.

[0268] The internal area of ​​the robot 6400 is equipped with a lithium ion battery 6409 according to one embodiment of the present invention and a semiconductor device or an electronic component. When the positive electrode active material according to one embodiment of the present invention is used in a lithium ion battery, a secondary battery with high capacity, high discharge capacity and good cycle characteristics can be realized.

[0269] Fig.22D An example of a sweeping robot is shown. The sweeping robot 6300 includes a display unit 6302 disposed on the top surface of a frame 6301, a plurality of cameras 6303 disposed on the side, a brush 6304, an operation button 6305, a lithium-ion battery 6306, various sensors, etc. Although not shown in the figure, the sweeping robot 6300 also has wheels, a suction port, etc. The sweeping robot 6300 can walk by itself and can detect garbage 6310 and suck the garbage from the suction port disposed below.

[0270] For example, the sweeping robot 6300 can determine whether there are obstacles such as walls, furniture, or steps by analyzing the image taken by the camera 6303. In addition, when objects such as wires that may be entangled with the brush 6304 are found through image analysis, the rotation of the brush 6304 can be stopped. The internal area of ​​the sweeping robot 6300 is equipped with a lithium ion battery 6306 and a semiconductor device or an electronic component according to one embodiment of the present invention. When the positive electrode active material of one embodiment of the present invention is used for a lithium ion battery, a secondary battery with high capacity, high discharge capacity and good cycle characteristics can be achieved.

[0271] This embodiment mode can be implemented in combination with other embodiment modes as appropriate.

[0272] Implementation 7 In this embodiment, an example in which a lithium ion battery according to one embodiment of the present invention is mounted on space equipment will be described.

[0273] Fig.23A As an example of a space device, an artificial satellite 6800 is shown. The artificial satellite 6800 includes a main body 6801, a solar panel 6802, an antenna 6803, and a lithium-ion battery 6805. A solar panel is sometimes referred to as a solar cell module.

[0274] When sunlight shines on the solar panel 6802, the power required for the artificial satellite 6800 to operate is generated. However, for example, when sunlight does not shine on the solar panel or when the amount of sunlight shining on the solar panel is small, the amount of electricity generated is reduced. Therefore, it is possible that the power required for the artificial satellite 6800 to operate will not be generated. In order to operate the artificial satellite 6800 even when the generated power is small, a lithium ion battery 6805 is preferably provided in the artificial satellite 6800. When the positive electrode active material of one embodiment of the present invention is used for a lithium ion battery, a secondary battery with high capacity, high discharge capacity and good cycle characteristics can be realized.

[0275] The artificial satellite 6800 can generate a signal. The signal is transmitted via the antenna 6803, and a receiver on the ground or another artificial satellite can receive the signal. By receiving the signal transmitted by the artificial satellite 6800, for example, the position of the receiver receiving the signal can be measured. Thus, the artificial satellite 6800 can constitute a satellite positioning system, for example.

[0276] Alternatively, the artificial satellite 6800 may include a sensor. For example, by including a visible light sensor, the artificial satellite 6800 may have a function of detecting sunlight reflected from an object on the ground. Alternatively, by including a thermal infrared sensor, the artificial satellite 6800 may have a function of detecting thermal infrared rays released from the ground. Thus, the artificial satellite 6800 may be used as an earth observation satellite, for example.

[0277] Fig. 23B As an example of space equipment, a probe 6900 including a solar sail (also called a light sail) is shown. The probe 6900 includes a main body 6901, a solar sail 6902, and a lithium-ion battery 6905. When the positive electrode active material of one embodiment of the present invention is used for a lithium-ion battery, a secondary battery with high capacity, high discharge capacity, and good cycle characteristics can be realized. When photons emitted by the sun irradiate the surface of the solar sail 6902, the momentum is transmitted to the solar sail 6902. Therefore, it is preferred that the surface of the solar sail 6902 has a high reflectivity film and faces the direction of the sun.

[0278] In addition, the solar sail 6902 can also be designed to be folded into a smaller state before leaving the atmosphere, and to unfold into a larger state when entering the outer atmosphere of the earth (space). Fig. 23B The large flakes shown.

[0279] exist Fig.23C, a spacecraft 6910 is shown as an example of a space device. The spacecraft 6910 includes a main body 6911, a solar panel 6912, and a lithium-ion battery 6913. When the positive electrode active material of one embodiment of the present invention is used for a lithium-ion battery, a secondary battery with high capacity, high discharge capacity, and good cycle characteristics can be achieved. The main body 6911 may include a pressurized cabin and a non-pressurized cabin, for example. The pressurized cabin may also be of a specification that is accessible to passengers. The electricity generated by sunlight irradiating the solar panel 6912 can be charged to the lithium-ion battery 6913.

[0280] exist Fig.23D 69, as an example of space equipment, a rover 6920 is shown. The rover 6920 includes a main body 6921 and a lithium-ion battery 6923. When the positive electrode active material of one embodiment of the present invention is used for a lithium-ion battery, a secondary battery with high capacity, high discharge capacity and good cycle characteristics can be realized. The rover 6920 may also include a solar panel 6922.

[0281] The rover 6920 may also be a passenger-accessible specification. The lithium-ion battery 6923 may be charged with electricity generated by sunlight hitting the solar panel 6912, or may be charged with electricity generated by other power sources such as a fuel cell or a radioisotope heat converter.

[0282] The content of this embodiment mode can be combined with the content of other embodiment modes as appropriate. Example 1

[0283] In this example, a positive electrode active material according to one embodiment of the present invention was produced and its characteristics were analyzed to evaluate the electrochemical characteristics.

[0284] <Manufacturing of positive electrode active material> according to Figure 2 The positive electrode active material of one embodiment of the present invention is synthesized as shown in the flow chart. Figure 2 As shown, commercially available LCO powder is doped with magnesium, nickel and aluminum.

[0285] MgF2 (purity: 99.9%), LiF (purity: 99%), Ni(OH)2 (purity: 99.9%), Al(OH)3 (purity: 99.99%), and LiCoO2 (purity: 99%, C-10N, manufactured by Nippon Chemical Industry Co., Ltd.) were used for the synthesis. In addition, C-10N without any treatment was used as the original LCO for the comparative example.

[0286] A muffle furnace was used in all heating steps and the samples were placed in alumina crucibles.

[0287] First, the original LCO (D50 12.5 μm) is preheated at 850°C for 2 hours in an oxygen atmosphere without adding additional elements. In the first addition process, the preheated LCO, MgF2, and LiF are weighed and mixed in a molar ratio of 1:0.01:0.003. The mixture is heated at 900°C for 20 hours in an oxygen atmosphere. In the second addition process, the LCO, Ni(OH)2, and Al(OH)3 obtained by the first addition process are mixed in a molar ratio of 1:0.005:0.005. The mixture is heated at 850°C for 10 hours in an oxygen atmosphere.

[0288] For comparison, only Mg(OH)2, MgF2-LiF, LiF-Ni(OH)2, LiF-Al(OH)3, LiF-Ni(OH)2-Al(OH)3, LiF, Ni(OH)2-Al(OH)3, MgF2-LiF-Ni(OH)2, MgF2-LiF-Al(OH)3 were added and synthesized in the same steps to obtain M-LCO, MF-LCO, FN-LCO, FA-LCO, FNA-LCO, F-LCO, NA-LCO, MFN-LCO and MFA-LCO. No elements were added to the LCO that was only heated, and only the same first and second heatings were performed. No heating process was performed on the original LCO.

[0289] To synthesize M-LCO, Mg(OH)2 was mixed with preheated LCO at a molar ratio of 1:0.01, and heated in the same manner as in the first addition step. To synthesize MF-LCO, preheated LCO, MgF2, and LiF were mixed at a molar ratio of 1:0.01:0.003, and heated in the same manner as in the first addition step. Finally, these products were heated in the same manner as in the second addition step without adding the additive element, thereby obtaining the final product.

[0290] For FN-LCO, FA-LCO, FNA-LCO and F-LCO, preheated LCO and LiF were mixed at a molar ratio of 1:0.023, and heated in the same manner as the first adding step. Ni(OH)2 or Al(OH)3 was mixed at a molar ratio of 1:0.005 with the obtained LCO, or Ni(OH)2 and Al(OH)3 were mixed at a molar ratio of 1:0.005:0.005 with the obtained LCO, and then a heating step was performed in the same manner as the second adding step.

[0291] In the synthesis of NA-LCO, no additional elements are added to the LCO preheated before the first heating. Ni(OH)2 and Al(OH)3 are mixed in a molar ratio of 1:0.005:0.005 with the LCO that has been heated for the first time, and then the second heating process is performed. In the synthesis of MFN-LCO and MFA-LCO, the preheated LCO, MgF2 and LiF are mixed in a molar ratio of 1:0.01:0.003, and then the first heating process is performed. Ni(OH)2 or Al(OH)3 is mixed in a molar ratio of 1:0.005 with the obtained LCO, and then the second heating process is performed. In addition, LCO that has not been added with any elements and has only been heated is also manufactured through the first heating process and the second heating process.

[0292] <Morphology and structure analysis> 《XRD》 Fig.24A , Fig. 24B and Fig.24C The powder XRD patterns of the positive electrode active material of one embodiment of the present invention and the original LCO and the reference pattern are shown. The powder XRD patterns of the positive electrode active material of one embodiment of the present invention and the original LCO show an O3 phase and a space group R-3m, and no other phases are observed.

[0293] In addition, Table 2 shows the results of Rietveld refinement of the powder XRD patterns of various samples. In Rietveld refinement, DIFFRAC.TOPAS ver.6 was used to analyze the single phase of LiCoO2 as the space group R-3m. The reason why the c-axis length of the positive electrode active material of one embodiment of the present invention is slightly longer than that of the original LCO may be due to the doping of nickel and aluminum. In addition, since the change in the a-axis length is extremely small, it can be considered that the amount of magnesium substituted to the cobalt position is small.

[0294] [Table 2]

[0295] SEM Fig.25A and Fig.25B A scanning electron microscope (SEM) image of pristine LCO is shown. Fig.25C and Fig.25D A SEM image of a positive electrode active material according to one embodiment of the present invention is shown. Fig.25A and Fig.25C The bars in the figure are 10 μm. Fig.25B and Fig.25D The bars in the figure are 2 μm. SEM images were obtained using a Hitachi SU4800 or SU8030 field emission SEM (FE-SEM) with an accelerating voltage of 5 kV.

[0296] This shows that the surface of the positive electrode active material of one embodiment of the present invention is smoother than the surface of the original LCO. This is probably because the surface of the LCO particles and the fluoride molten salt partially melted during the heating process.

[0297] 《SEM-EDX》 FIG. 26A to FIG. 27F SEM-EDX mapping images of the positive electrode active material of one embodiment of the present invention in each step of synthesis are shown. SEM images were obtained using a Hitachi SU4800 or SU8030 field emission SEM (FE-SEM) at an accelerating voltage of 5 kV. SEM-EDX was performed using an EMAX Evolution EX-370 (manufactured by HORIBA) at an accelerating voltage of 15 kV. Fig.26A and Fig.26B is the SEM image of pristine LCO, Fig.26C and Fig.26D is a SEM image of preheated LCO. Fig.26E and Fig.26F This is a SEM image of a preheated mixture of LCO, LiF and MgF2. Figure 26G is with Fig.26F SEM-EDX mapping images of each element in the same area. Fig.26H and Fig.26I This is a SEM image of LCO with magnesium and fluorine added. Fig.26J is with Fig.26I SEM-EDX mapping images of each element in the same area. Fig.27A and Fig.27B This is a SEM image of a mixture of LCO, Ni(OH)2 and Al(OH)3 with magnesium and fluorine added. Fig.27C is with Fig.27B SEM-EDX mapping images of each element in the same area. Fig.27D and Fig.27E This is a SEM image of a positive electrode active material according to one embodiment of the present invention. Fig.27F is with Fig.27E SEM-EDX mapping images of each element in the same area. Fig.26A , Fig.26C , Fig.26E , Fig.26H , Fig.27A and Fig.27D The bars in the figure are 50 μm. Fig.26B , Fig.26D , Fig.26F , Figure 26G , Fig.26I , Fig.26J , Fig.27B , Fig.27C , Fig.27E and Fig.27FThe bars in the figure are 5 μm.

[0298] like FIG. 26E to FIG. 26J As shown in FIG. 1 , SEM-EDX can confirm that the added MgF2-LiF nanoparticles melt due to heating and wet and spread on the surface of the lithium cobalt oxide particles. FIG. 27D to FIG. 27F As shown, in the EDX element mapping analysis of the positive electrode active material particles according to one embodiment of the present invention, magnesium, nickel, and aluminum are uniformly distributed, and nanoparticles composed of these added elements are not observed.

[0299] ICP-MS In the synthesis of the positive electrode active material of one embodiment of the present invention, the element ratio is Co:Mg:F=1:0.01:0.023. Table 3 shows the results of quantitative analysis of the added elements using inductively coupled plasma mass spectrometry (ICP-MS). ICP-MS analysis was performed using agilent 8900. As shown in Table 3, it was confirmed that the element ratio of Co:Mg in the positive electrode active material particles of one embodiment of the present invention was 1:0.0093.

[0300] [Table 3]

[0301] EPMA As shown in Table 4, the cross section of the positive electrode active material particle of one embodiment of the present invention was also confirmed to be Co:Mg=1:0.009 by electron probe microanalyzer (EPMA). In the EPMA analysis, JXA-iHP200F (JEOL) was used, and the accelerating voltage was 10 kV. In order to analyze the elements of the bulk, the center of the particle cross section was measured.

[0302] [Table 4]

[0303] XPS However, in X-ray photoelectron spectroscopy (XPS), the ratio of magnesium and fluorine to cobalt in the positive electrode active material of one embodiment of the present invention is significantly higher than the amount added to the original LCO during synthesis, from which it can be seen that magnesium and fluorine are distributed in large quantities on the outermost surface of the particles of the positive electrode active material of one embodiment of the present invention. The element ratio measured by XPS is Co:Mg:F=1:0.93:0.53.

[0304] Table 5 shows the XPS analysis results of the original LCO, the positive electrode active material of one embodiment of the present invention, and Figure 2The chemical composition of the particle surface of the samples with asterisks in the figure. XPS measurements were recorded using a spectrometer (Quantera-SXM, ULVAC-PHI) equipped with an Al X-ray source (1486.6 eV). All bond energies were corrected using the C1s peak at 284.8 eV.

[0305] [Table 5]

[0306] Figures 28 to 29B The characteristic evaluation of the positive electrode active material according to one embodiment of the present invention using XPS is shown. Fig.28 It is the XPS wide scan spectrum of the original LCO and the positive electrode active material of one embodiment of the present invention. Fig.29A XPS narrow scan spectra of F1s of a positive electrode active material according to one embodiment of the present invention, LCO to which magnesium and fluorine are added, a mixture of preheated LCO, LiF and MgF2, MgF2 (reference sample), and LiF (reference sample) are shown. Fig.29B The XPS narrow scan spectrum of Mg1s is shown.

[0307] like Fig.29A As shown in FIG. 1 , the bond energy of F1s in the positive electrode active material of one embodiment of the present invention is different from that of MgF2 used as an additive element source. Fig.29B As shown, the bond energy of Mg1s of the positive electrode active material of one embodiment of the present invention indicates the presence of fluoride oxide. The Mg1s peak of the positive electrode active material of one embodiment of the present invention (maximum value of 1303.6 eV above 1300 eV and below 1308 eV) is located between the peaks of MgO (1303.3 eV) and MgF2 (1306.3 eV).

[0308] 《HAADF-STEM, NBED》 Fig.25E A high-angle annular dark field-scanning transmission electron microscopy (HAADF-STEM) image of a particle surface portion including pristine LCO is shown. Fig.25F yes Fig.25E Magnified view of the area surrounded by the dotted rectangle in . Figure 25G Show Fig.25E Nanobeam electron diffraction (NBED) patterns of area 1 and area 2 marked in FIG. Cross-sectional HAADF-STEM observation and NBED measurement were performed using a spherical aberration-corrected STEM JEM-ARM200F manufactured by JEOL at an accelerating voltage of 200 kV.

[0309] like Fig.25E and Fig.25FAs shown, a small amount of cations are mixed near the surface. Regions 1 and 2 are both patterns showing a layered rock salt type crystal structure. It is known that the surface layer of the original LCO particle has a layered rock salt structure similar to its internal structure.

[0310] Fig.25H is a HAADF-STEM image of the surface of a particle of a positive electrode active material according to one embodiment of the present invention. Fig.25I yes Fig.25H Magnified view of the area surrounded by the dotted rectangle in . Fig.25J Show Fig.25H NBED patterns of area 3 and area 4 marked in FIG. Area 3 is a pattern showing a rock salt type crystal structure, and area 4 is a pattern showing a layered rock salt type crystal structure.

[0311] Notice, FIG. 25E to FIG. 25I The scale bars in the figures are all 3 nm. Figure 25G and Fig.25J The incident direction of the electron beam and the index of a part of the spot are shown. Fig.25J The spots (dashed circles) representing the rock salt type structure and the spots (solid circles) representing the layered rock salt structure are included.

[0312] In Fig.25I When the dotted line in is marked, it can be seen that the layered rock salt type crystal structure (region I) and the rock salt crystal structure (region II) are continuously bonded. Fig.25H and Fig.25I As shown, the inner side (also referred to as the bulk region) of the positive electrode active material of one embodiment of the present invention has a layered rock salt structure, and the contrast between the Co layer and the Li layer is observed in the HAADF-STEM image. Cation mixing is also observed. A rock salt structure with a thickness of 1 nm (represented by electron diffraction spots surrounded by dotted circles) is observed in the outermost surface region, and a layered rock salt structure (represented by electron diffraction spots surrounded by solid circles) is also included.

[0313] It should be noted that if Fig.25I As shown, since the arrangement of the atomic columns is continuous between regions I and II, the rock salt shell (region II) is continuously bonded to the layered rock salt core (region I). As shown in the XPS results, such a rock salt shell contains lithium in an amount similar to that of cobalt and magnesium, so it can be inferred that lithium ions pass through the shell.

[0314] That is, lithium ions can pass through the shell through the position where lithium exists in the post-synthesis stage in the rock salt crystal structure. At this time, when the ratio of lithium to cation positions Li / (Li+Co+Mg+Ni+Al) is, for example, 20% or more, the critical permeation probability of the face-centered cubic lattice is exceeded, so Li ions can be embedded and detached. In addition, cation defects may also become Li diffusion paths, so even if the above-mentioned lithium-to-cation defect ratio (Li+cation defect) / (Li+Co+Mg+Ni+Al+cation defect) is 20% or more, Li ions can be embedded and detached.

[0315] STEM-EDX FIG. 30A to FIG. 31 Energy dispersive X-ray (EDX) elemental analysis of the positive electrode active material according to one embodiment of the present invention is shown.

[0316] Fig. 30A HAADF-STEM image and the corresponding STEM / EDX elemental mapping analysis of Co, F, Mg, Ni and Al. The bar is 5 nm. Fig. 30B is the depth distribution of the element distribution. Fig. 30C yes Fig. 30B Magnified image of . Fig.31 This is a wide-range HAADF-STEM image of the surface of the positive electrode active material particle of one embodiment of the present invention and the corresponding STEM / EDX elemental mapping analysis of Co, F, Mg, Ni, and Al. The bar is 50 nm. The cross-sectional STEM-EDX analysis was performed using a JED-2300T (JEOL).

[0317] From the above, it can be seen that F, Mg, and Ni are evenly distributed on the entire outermost surface, but in this measurement, there are very few F, Mg, and Ni in the bulk. Al was observed in a wide area on the particle surface. A clear gradient of the added element was observed near the surface of the positive electrode active material of one embodiment of the present invention. These observations indicate that a topological phase transition from layered rock salt to rock salt structure occurs during the synthesis, and the phase transition is caused by the structural movement of the added element to the LCO.

[0318] The distribution of the additional elements in the particle surface of the positive electrode active material according to one embodiment of the present invention can be explained as follows. First, the distribution of the additional elements in the particle surface of the positive electrode active material according to one embodiment of the present invention can be explained as follows. 2+ The solubility of Al is about 0.5%. 3+ LiAl x Co 1- x O2 can form a solid solution with lithium cobalt oxide. Secondly, MgO, CoO, and NiO form a solid solution with a rock salt structure. 2+ Ions and Ni 2+Ions may replace Co in the CoO region of the surface layer of lithium cobalt oxide particles formed by reduction of the surface region during high-temperature heating. 2+ ions. Therefore, the rock salt layer in the surface layer of lithium cobalt oxide contains a considerable amount of Mg and Ni. On the other hand, based on the c-axis extension state observed by XRD and EPMA analysis, it is considered that most of the added magnesium is dissolved in the LCO particles. The distribution of the added elements is achieved by combining the molten salts of LiF and MgF2 with appropriate heating steps.

[0319] Morphology and Structure Analysis of the Cathode Active Material of One Embodiment of the Present Invention at Each Stage of Synthesis The following describes the detailed characteristics of the cathode active material of one embodiment of the present invention in each process of the synthesis process.

[0320] To evaluate the structural characteristics, SEM-EDX, XPS, and XRD measurements are performed at each stage of the synthesis process of the cathode active material of one embodiment of the present invention. The analysis is carried out at the following stages, which are marked with asterisks in the Figure 2 synthesis flow chart of the cathode active material of one embodiment of the present invention shown. - Raw LCO - Preheated LCO - Mixture of preheated LCO, LiF, and MgF2 - LCO added with magnesium and fluorine - Mixture of LCO added with magnesium and fluorine, Ni(OH)2, and Al(OH)3 - Cathode active material of one embodiment of the present invention

[0321] <SEM-EDX Analysis> According to the results of SEM-EDX ( FIG. 26A to FIG. 27F ), the state of the particle surface in each process is as follows. The raw LCO has a large amount of damage and attachments on the particle surface. The surface of the preheated LCO particles is smoother than that of the raw LCO. Nanoparticles of MgF2 and LiF are sparsely present on the particles of the mixture of preheated LCO, LiF, and MgF2. After the first heating process, the surface of the LCO added with magnesium and fluorine becomes smooth, and no nanoparticles containing Mg and F on the surface of the LCO particles are observed in SEM-EDX, indicating that MgF2 and LiF are melted on the LCO surface.

[0322] The particle surface of the mixture of LCO, Ni(OH)2, and Al(OH)3 added with magnesium and fluorine is uniformly covered with nanoparticles of Ni(OH)2 and Al(OH)3. Different from the mixture of LCO, Ni(OH)2, and Al(OH)3 added with magnesium and fluorine, the particle surface of the positive electrode active material of one embodiment of the present invention is smooth and is observed to be uniformly covered with Mg, F, Ni, and Al in SEM-EDX.

[0323] <XPS Analysis> Figures 28 to 29B And Table 5 shows the XPS measurement results. A large amount of magnesium and fluorine are detected by XPS from the pre-heated mixture of LCO, LiF, and MgF2. This is because, as can be seen from the SEM image, nanoparticles of MgF2 and LiF adhere to the LCO surface. The amount of magnesium detected in the LCO added with magnesium and fluorine after the first heating is more than that before the first heating. It is speculated that this phenomenon is due to an increase in the amount of magnesium in the XPS detection region at a depth of about 5 nm from the surface. This increase is caused by the melting and diffusion of magnesium on the surface of the lithium cobaltate particles due to the effect of the fluoride molten salt. The detected amount of fluorine is less than that in the previous process, which is considered to be because a part of LiF melts and volatilizes. An extremely large amount of nickel and aluminum are detected from the mixture of LCO, Ni(OH)2, and Al(OH)3 added with magnesium and fluorine. It is considered that this is because, as shown in the SEM image, nanoparticles of Ni(OH)2 and Al(OH)3 cover the particle surface. In the positive electrode active material of one embodiment of the present invention, the detected amounts of nickel and aluminum are less than those in the mixture of LCO, Ni(OH)2, and Al(OH)3 added with magnesium and fluorine. This indicates that nickel and aluminum form a solid solution in the surface layer part of the lithium cobaltate particles. Furthermore, since the detected amount of magnesium is more than the detected amounts of nickel and aluminum, it can be seen that magnesium is located on the outermost surface of the LCO particles, and nickel and aluminum are located inside the outermost surface.

[0324] Fig.29A And Fig.29B shows the bond energy between F and Mg. The bond energy between F1s and Mg1s in the pre-heated mixture of LCO, LiF, and MgF2 indicates the presence of MgF2. However, the LCO added with magnesium and fluorine shows a different bond energy, which indicates the presence of the O-Mg-F bond. The O-Mg-F bond is also maintained in the positive electrode active material of one embodiment of the present invention added with Ni(OH)2 and Al(OH)3.

[0325] <XRD Analysis> Table 6 shows the results of Rietveld refinement of the powder XRD pattern. The lattice constant of the pre-heated LCO is smaller than that of the original LCO, which is considered to be because the mixing of cations decreases and the crystallinity increases. The c-axis length of the LCO added with magnesium and fluorine increases compared with the c-axis length of the pre-heated mixture of LCO, LiF, and MgF2. This means that compared with Co3+ Mg with large ionic radius 2+ Substituted by cobalt or have Li + Mg with the same ionic radius 2+ The valence of the adjacent cobalt replaced by the lithium position is changed from 3 to 2 for charge compensation. The positive electrode active material of one embodiment of the present invention also maintains an extended c-axis. This means that as shown in XPS, not only the surface of the positive electrode active material of one embodiment of the present invention is covered with a large amount of magnesium, but also the bulk of the positive electrode active material of one embodiment of the present invention is doped with magnesium.

[0326] [Table 6]

[0327] <Electrochemical Performance> Half Battery Fig.32A and Fig.32B The cycle characteristics of a positive electrode including pristine LCO and a positive electrode including a positive electrode active material according to one embodiment of the present invention in a half-cell are shown. Fig.32A and Fig.32B The cycle performance of an electrode including pristine LCO and an electrode including a positive electrode active material according to one embodiment of the present invention in a coin-type half-cell at 25° C. is shown. Fig.32A and Fig.32B The voltages from 2.5V to 4.6V (vs.Li + / Li) and 2.5V to 4.7V (vs.Li + The charge-discharge cycle performance of a half-cell using a positive electrode including a pristine LCO and a half-cell using a positive electrode including a positive electrode active material according to one embodiment of the present invention are compared within a voltage range of 1000 W / Li. Fig.33A is Fig.32A The charge and discharge curves of the original LCO and the positive electrode active material of one embodiment of the present invention in different cycles under the conditions shown. Fig.33B The rate performance of a half-cell using the original LCO and a half-cell using the positive electrode active material of one embodiment of the present invention is shown. Fig.32A and Fig.32B In the figure, white circles represent the coulombic efficiency of the positive electrode active material of one embodiment of the present invention, and black circles represent the discharge capacity of the positive electrode active material of one embodiment of the present invention. In addition, white squares represent the coulombic efficiency of the original LCO, and black squares represent the discharge capacity of the original LCO. Fig.35A , Fig.39A and Fig.39B The same is true.

[0328] When using a commonly used electrolyte, the positive electrode active material of one embodiment of the present invention shows a relatively high capacity retention rate compared to the original LCO. Specifically, the capacity retention rate of the positive electrode active material of one embodiment of the present invention after 100 cycles is between 2.5V and 4.6V (vs. Li + / Li) is 96.4% (205.2mAh / g), and at 2.5V to 4.7V (vs.Li + / Li) was 72.7% (160.9 mAh / g), which is much higher than that of pristine LCO. The high coulombic efficiency observed in the cycle of the positive electrode active material of one embodiment of the present invention means that the decomposition of the oxidizing electrolyte is effectively suppressed by the surface coating.

[0329] Fig.33A The charge / discharge curves shown in FIG. 1 show that the average discharge voltage of the positive electrode active material of one embodiment of the present invention remains high after 100 cycles. On the other hand, the average discharge voltage of the original LCO decreases with increasing voltage polarization. Fig.33B As shown in FIG. 1 , at each discharge rate, the positive electrode active material of one embodiment of the present invention exhibits better rate performance than the original LCO. Fig.34 As shown, the positive electrode active material of one embodiment of the present invention can be used even at a high loading amount (20 mg / cm 2 ) can also be charged and discharged at a high rate. Fig.33B In the graph, white circles represent the discharge capacity of the positive electrode active material according to one embodiment of the present invention, and black squares represent the discharge capacity of the original LCO.

[0330] In the initial charge and discharge cycle of the positive electrode active material of one embodiment of the present invention, the cell resistance decreases and the discharge capacity increases. This phenomenon is caused by the formation of a solid electrolyte interphase (SEI) on the surface of lithium cobalt oxide and the diffusion of magnesium into the structure of lithium cobalt oxide.

[0331] Considering that the general electrolyte may be 4.7V (vs.Li + / Li) due to the high cutoff voltage, a modified fluorine electrolyte was used instead of a general electrolyte to manufacture a half-cell. In addition, in order to reduce the impact of electrolyte decomposition, an electrode with a high charge and discharge rate and a low mass load was used to evaluate the cycle performance.

[0332] Fig.35A The results show that the half-cell including the positive electrode active material of one embodiment of the present invention using a fluorine-based electrolyte and the half-cell including the positive electrode of the original LCO have a high charge / discharge rate at 2.5 V to 4.7 V (vs. Li + / Li) cycle performance in the voltage range. Fig.35B is Fig.35AThe charge and discharge curves of the original LCO and the positive electrode active material of one embodiment of the present invention in different cycles under the conditions shown. As the electrolyte, 1M LiPF6 was dissolved in FEC / MTFP (volume ratio 2:8) and 5wt% PS was added. In the cycle performance test, the voltage range of 2.5V to 4.7V (vs. Li + / Li) were subjected to CCCV charging at 200 mA / g and final current 40 mA / g and CC discharging at 200 mA / g. A rest time of 1 minute was set after each charge and discharge step. The measurement environment was 25°C.

[0333] By adopting this method, Fig.35A and Fig.35B As shown, at 200mA / g, the voltage range is 2.5V to 4.7V (vs.Li + / Li) under the condition of high capacity retention of 88.5% (191.5 mAh / g) was obtained after 100 cycles.

[0334] The half-cell is manufactured by the following method. 95wt% of active material, 3wt% of carbon black (DENKABLACK (registered trademark), manufactured by Denka) as a conductive aid, and 2wt% of polyvinylidene fluoride as a binder are mixed to manufacture the LCO positive electrode. The weighed powder is mixed in N-methyl-1,2-pyrrolidone (NMP, 99.9%, manufactured by Tokyo Chemical Industry Co., Ltd.) to make a uniform slurry. Use a scraper to apply the slurry on an aluminum foil current collector. In a forced convection drying oven, the NMP solvent is dried at 80°C for 0.5 hours. The mass loading of the active material is basically controlled to 7mg / cm 2 Around, but Fig.33A and Fig.33B as well as Fig.35A and Fig.35B The data is controlled to 20mg / cm 2 Around and 3mg / cm 2 A coin-type half-cell (CR2032) was assembled in an argon-filled glove box using the manufactured positive electrode, a lithium metal foil (thickness 0.6 mm, purity 99.9%, manufactured by Honjo Metal Industries, Ltd.) as a counter electrode, polypropylene (PP) as a separator, and an electrolyte.

[0335] Two types of electrolytes are used for half-cells. One is a general electrolyte in which LiPF6 is dissolved in ethylene carbonate / diethyl carbonate (EC / DEC=volume ratio 3:7) to make 1M and 2wt% of vinylene carbonate (VC) is added as an additive. The other is a fluorine-based electrolyte in which LiPF6 is dissolved in fluoroethylene carbonate / methyl 3,3,3-trifluoropropionate (FEC / MTFP, volume ratio 2:8) to make 1M and 5wt% of 1,3-propane sultone (PS) is added as an additive. Unless otherwise specified, a common electrolyte is used.

[0336] The charge and discharge measurements were performed using a TOSCAT-3100 (manufactured by Toyo Systems Co., Ltd.) battery test system and a temperature-controlled processing chamber at 25°C. The cycle performance of the half-cell was tested at 2.5V to 4.6V or 2.5V to 4.7V (vs. Li + The battery was charged at a constant current-constant voltage (CCCV) of 100 mA / g, discharged at a final current of 10 mA / g, and discharged at a constant current (CC) of 100 mA / g in a voltage range of 100 mA / g / Li. The capacity retention rate after 100 cycles was calculated using the maximum discharge capacity obtained in the cycle test.

[0337] exist Fig.33B The discharge rate performance test shown was performed with constant current-constant voltage (CCCV) charging at 100 mA / g, using a final current of 10 mA / g, followed by CC discharge over a voltage range of 2.5 V to 4.7 V (vs. Li + / Li). The CC discharge current was changed every five cycles as follows: 40 mA / g, 100 mA / g, 200 mA / g, 400 mA / g, 600 mA / g, 1000 mA / g, 2000 mA / g, 100 mA / g. A rest time of 10 minutes was set after each charge and discharge step.

[0338] exist Fig.34 In the experiment shown, the following discharge rate test was performed, constant current constant voltage (CCCV) charging at 40 mA / g, using a final current of 4 mA / g, and then at 2.5 V to 4.7 V (vs. Li + / Li) was used for CC discharge. The CC discharge current was changed every five cycles as follows: 40 mA / g, 100 mA / g, 200 mA / g, 400 mA / g, 600 mA / g, 1000 mA / g, 40 mA / g. A rest time of 10 minutes was set after each charge and discharge step.

[0339] Full Battery In order to evaluate the electrochemical performance under more practical conditions, a pouch-type full cell having the same structure as a commercial product was manufactured using a positive electrode including the positive electrode active material of one embodiment of the present invention and a negative electrode including commercially available graphite.

[0340] The positive electrode was manufactured in the same manner as the half-cell. As the negative electrode, 96 wt% of artificial graphite (MCMB: mesocarbon micro Beads graphite G10, Linyi Gelon Lib Co., Ltd.) was used as the active material, 1 wt% of vapor-grown carbon nanofiber (VGCF (registered trademark)-H, Showa Denko Co.) was used as the conductive aid, 1 wt% of sodium carboxymethyl cellulose (CMC, manufactured by KISHIDACHEMICAL Co., Ltd.) was used as the thickener, and 2 wt% of styrene-butadiene rubber (SBR, TRD2001, manufactured by JSR Co., Ltd.) was used as the binder.

[0341] The weighed negative electrode active material, conductive additive, thickener and binder powders were mixed with distilled water to prepare a slurry, which was then coated on the copper foil current collector. The mass loading of the positive and negative electrodes was 10.6 mg / cm 2 and 7.6mg / cm 2 , with dimensions of 41mm×50mm and 45mm×53mm respectively. The battery design goal is to achieve a positive electrode to negative electrode capacity ratio of about 80%, a positive electrode and a negative electrode capacity of 200mAh / g and 300mAh / g respectively, and a total battery capacity of 40mAh. The pouch-type full battery is assembled using a lamination process in an argon-filled glove box. In this process, a single-sided coated negative and positive electrode sheet, a separator made of polypropylene (PP), and an electrolyte in which 1M LiPF6 is dissolved in FEC / MTFP (volume ratio 2:8) are used.

[0342] The full cell manufactured as described above was subjected to the following cycle performance test, with CCCV charging (40 mA / g, final current 4 mA / g) and CC discharge (40 mA / g) performed in the voltage range of 3.0 V to 4.5 V (vs. graphite) or 3.0 V to 4.6 V (vs. graphite). A rest time of 1 minute was set after each charging and discharging step.

[0343] Fig.36A and Fig.36B The electrochemical performance of the pouch-type full cell at 25° C. is shown. Fig.36A and Fig.36B The cycle performances of pouch-type full cells using a positive electrode including the positive electrode active material of one embodiment of the present invention in the voltage ranges of 3.0 V to 4.5 V and 3.0 V to 4.6 V are shown (vs. graphite).

[0344] The energy density retention rate of each full cell after 500 cycles at 25°C was 90.3% (656.8Wh / kg) in the voltage range of 3.0V to 4.5V and 75.8% (593.4Wh / kg) in the voltage range of 3.0V to 4.6V (vs. graphite). Compared with previous studies on doping and coating of LCO at high voltage (e.g., non-patent document 7, non-patent document 12, and non-patent document 17), the full cell using the positive electrode active material of one embodiment of the present invention exhibited very stable cycle performance.

[0345] <Analysis of the positive electrode active material of one embodiment of the present invention and the original LCO after the cycle test> Fig.37A Ex situ XRD patterns of a positive electrode including pristine LCO and a positive electrode including a positive electrode active material according to one embodiment of the present invention in a discharged state after 100 cycles are shown. Fig.37B This is an enlarged view of the range of 2θ from 18° to 19.5°. Fig.37C This is an enlarged view of the 2θ range of 44.5° to 45.5°.

[0346] In order to carry out Fig.37A and Fig.37B The measurements of the original LCO and the positive electrode active material of one embodiment of the present invention were performed using a coin-type half-cell using a common electrolyte. The ex situ XRD of the positive electrode containing the original LCO and the positive electrode containing the positive electrode active material of one embodiment of the present invention in the discharge state after 100 cycles showed that the positive electrode contained the original LCO and the positive electrode active material contained in one embodiment of the present invention had a voltage range of 2.5V to 4.7V (vs. Li + / Li), the battery was cycled by CCCV charge (40 mA / g, final current 10 mA / g) and CC discharge (40 mA / g).

[0347] XRD measurements were performed using CuKα The powder samples were analyzed with a Bruker D8ADVANCE diffractometer. The scanning range (2θ) was 15° to 90°, the step width was 0.005°, and the scanning speed was 0.1 sec / step. Rietveld refinement was performed using DIFFRAC TOPAS V6 software (manufactured by Bruker). Subsequent ex situ XRD measurements were also performed under the same conditions.

[0348] like Fig.37A and Fig.37B As shown, in the discharged state after 100 cycles, the ex situ XRD pattern of the pristine LCO shows broad XRD peaks indicating low crystallinity.

[0349] Fig.37A and Fig.37BThe XRD pattern shown is a pattern obtained by removing the background and CuKα2 peaks using DIFFRAC.EVA. The background removal conditions were 25Curvature and 1e -5 Threshold.

[0350] It is known that the 003 of lithium cobalt oxide has a peak near 2θ=19° (in the range of 18° to 19.5°). The half width of the 003 peak in the original LCO (in this specification, the half width refers to the half-peak full width without special instructions) was 0.0325° before the charge and discharge cycle test, but it widened significantly to 0.1836° after 100 cycles of the charge and discharge cycle test, and drifted to the low angle side. In addition, it is known that the 104 of lithium cobalt oxide has a peak near 2θ=45° (in the range of 44.5° to 45.5°). The half width of the 104 peak in the original LCO was 0.0644° before the charge and discharge cycle test, but it also widened to 0.1594° after the same test.

[0351] However, the positive electrode active material of one embodiment of the present invention presents a sharp peak and maintains high crystallinity even after 100 cycles. The half width of the 003 peak of the positive electrode active material of one embodiment of the present invention is 0.0333° before the charge and discharge cycle test, and is also less than 0.10° after 100 cycles of the charge and discharge cycle test, specifically 0.0515°, which is a sufficiently sharp peak. In addition, the half width of the 104 peak before the charge and discharge cycle test is 0.0636°, and is less than 0.11° after the same test, specifically 0.0646°, which is also sufficiently sharp.

[0352] FIG. 38A to FIG. 38H SEM images of pristine LCO and a positive electrode active material according to one embodiment of the present invention in a discharged state after cycles are shown. Fig.38A and Fig.38B is the SEM image of the original LCO after five cycles, Fig.38C and Fig.38D is the SEM image of pristine LCO after 50 cycles. Fig.38E and Fig.38F is a SEM image of the positive electrode active material of one embodiment of the present invention after five cycles. Figure 38G and Figure 38H This is a SEM image of the positive electrode active material of one embodiment of the present invention after 50 cycles. Fig.39A The SEM images after five cycles are shown at 25°C and in the voltage range of 2.5 V to 4.7 V (vs. Li + Cycling performance of pristine LCO and the positive electrode active material of one embodiment of the present invention under conditions of 1:1 / Li. Fig.39BSEM images after 50 cycles are shown at 25°C and in the voltage range of 2.5V to 4.7V (vs. Li + Cycling performance of pristine LCO and the positive electrode active material of one embodiment of the present invention under conditions of 1:1 / Li. Fig.38A , Fig.38C , Fig.38E and Figure 38G The scale bar in the figure is 50 μm. Fig.38B , Fig.38D , Fig.38F and Figure 38H The scale bar in the figure is 5 μm. Fig.39A and Fig.39B In the graph, the Coulombic efficiency of the measurement points with a discharge capacity less than 10 mAh / g is not plotted.

[0353] like FIG. 38A to FIG. 38D As shown, in the SEM observation after the cycle test of the original LCO, fewer cracks were observed in the discharge state after five cycles. In particular, the cracks were clearly observed near the grain boundaries. The original LCO had more and larger cracks in the discharge state after 50 cycles. No cracks were observed in the positive electrode active material of one embodiment of the present invention in the discharge state after five cycles. Minor cracks were observed in the discharge state after 50 cycles.

[0354] Furthermore, HAADF-STEM images and NBED patterns of the original LCO and the cathode active material of one embodiment of the present invention after 50 cycles in the voltage range of 2.5 V to 4.7 V were obtained. Fig.40A HAADF-STEM image showing the surface of the original LCO particle. Fig.40B Show Fig.40A NBED patterns of regions 1 to 3 marked in FIG. Region 1 is a pattern showing a rock salt type crystal structure, region 2 is a pattern showing a spinel type crystal structure, and region 3 is a pattern showing a layered rock salt type crystal structure.

[0355] Fig.40C This is a HAADF-STEM image of the surface layer of the positive electrode active material particle according to one embodiment of the present invention. Fig.40D Show Fig.40C NBED patterns of area 4 and area 5 marked in FIG. Area 4 is a pattern showing a rock salt type crystal structure, and area 5 is a pattern showing a layered rock salt type crystal structure. Fig.40A and Fig.40C The scale bar in the figure is 3 nm.

[0356] Fig.40B It is shown that spinel and rock salt phases with a thickness of about 3 nm are formed in the surface layer of the original LCO. Fig.40C and Fig.40DAs shown, even after 50 cycles, the outermost surface of the positive electrode active material of one embodiment of the present invention maintains a rock salt structure with a thickness of about 1 nm.

[0357] The reason why spinel and rock salt phases are formed in the degraded original LCO surface layer is that oxygen is released from the LCO surface. However, in the surface layer of the positive electrode active material of one embodiment of the present invention, magnesium, nickel and aluminum are present at high concentrations, so the release of oxygen from the LCO surface under highly delithiation conditions is suppressed, thereby preventing the formation of the spinel region.

[0358] <Structural Analysis of the Positive Electrode Active Material of One Embodiment of the Invention under Highly Delithiation Conditions> 《Ex situ XRD》 In order to clarify the mechanism of improved characteristics, structural analysis during high voltage cycling was performed.

[0359] Generally speaking, it is known that LCO undergoes a phase transition from O3 phase to H1-3 phase when charged to 4.55 V (in Li x CoO2 (x<0.3). This structural change reduces the capacity retention rate of LCO at high voltage. It can be considered that the good electrochemical performance of the positive electrode active material of one embodiment of the present invention at high voltage is greatly correlated with the suppression of this phase transition, and ex situ XRD measurement is performed on the charged positive electrode taken out from the half-cell.

[0360] FIG. 41A to FIG. 42C Ex situ XRD patterns of a positive electrode including pristine LCO or a positive electrode including a positive electrode active material according to one embodiment of the present invention in various cycles are shown. Fig.41A The ex situ XRD patterns of the original LCO at the first and fifth charge states up to 4.7 V are shown in Figure 1. Fig.41B This is an enlarged view of the 2θ range of 18° or more and 21° or less. Fig.41C This is an enlarged view of the 2θ range of 42° or more and 48° or less. Fig.42A are ex situ XRD patterns of the positive electrode active material of one embodiment of the present invention in the first, second, fifth, and 50th charging states up to 4.7 V, Fig.42B This is an enlarged view of the 2θ range of 18° or more and 21° or less. Fig.42C This is an enlarged view of the 2θ range of 42° to 48°. The reference XRD pattern is Li 0.35 CoO2 (O3 phase) (Non-patent document 18 and ICSD collection code 172912), Li 0.12 CoO2 H1-3 phase (Non-Patent Document 19) and O3' phase described in this specification, etc. FIG. 41A to FIG. 44CIn the graph, the diamond (◇) is a peak derived from the existing O3 phase after delithiation, the triangle (△) is a peak derived from the H1-3 phase, and the circle (●) is a peak derived from the O3' phase.

[0361] In order to carry out FIG. 41A to FIG. 44C The ex situ XRD measurements shown were performed using a coin-type half-cell with a common electrolyte. FIG. 41A to FIG. 42C In the positive electrode including the original LCO and the positive electrode including the positive electrode active material of one embodiment of the present invention, the positive electrode was charged to 4.7 V with CC (10 mA / g) before the ex situ XRD measurement in the first, second, fifth, or 50th charge. Before the second, fifth, and 50th charge, the positive electrode was charged to 4.7 V with CC (10 mA / g). + The battery was cycled 1, 4, and 49 times by CCCV charging (100 mA / g, final current 10 mA / g) and CC discharging (100 mA / g) in a voltage range of 1:1.

[0362] Then, the positive electrode sheet of the charged or discharged battery was taken out in a glove box filled with argon and prepared for ex situ XRD measurement. The positive electrode sheet was cleaned with dimethyl carbonate to remove the electrolyte, dried and fixed to a flat glass substrate with double-sided tape. The samples were sealed on an airtight sample holder (Part No.: A100B33) in an argon glove box and XRD measurements were performed under argon atmosphere. The scanning range (2θ) was 15° to 75°, the step width was 0.01°, and the scanning speed was 1.0 sec / step.

[0363] like FIG. 41A to FIG. 41C As shown, in the case of the first charge of the original LCO at 4.7 V, the charge capacity is 239.4 mAh / g, and the Li concentration (Li x CoO2) is x=0.13, and the formation of H1-3 phase is confirmed by ex situ XRD.

[0364] in addition, FIG. 43A to FIG. 43C The exsitu XRD patterns of the positive electrode containing pristine LCO at a charged state of 4.6 V or 4.7 V are shown. Fig.43A The ex situ XRD patterns of the positive electrode containing pristine LCO at the first charge at 4.6 V or 4.7 V at 10 mA / g are shown. Fig.43B This is an enlarged view of the 2θ range of 18° or more and 21° or less. Fig.43C This is an enlarged view of the 2θ range of 42° or more and 48° or less.

[0365] like FIG. 43A to FIG. 43C As shown, even if the first charge is to 4.6V and the charge capacity is reduced to 224.6mAh / g (Lix In the case of CoO2 with x = 0.18), the formation of H1-3 phase was also observed.

[0366] like FIG. 41A to FIG. 41C As shown in Figure 1, in the sample charged for the fifth time at 4.7 V, it was observed that the surface layer of the original LCO was damaged due to exposure to high voltage, making lithium diffusion difficult, resulting in a charge capacity of 145.6 mAh / g (x = 0.47). The reversibility of the original LCO was severely reduced, so no Li x Phase transition from O3 phase to H1-3 phase at x < 0.3 in CoO2.

[0367] FIG. 42A to FIG. 42C An ex situ XRD pattern of a positive electrode including the positive electrode active material according to one embodiment of the present invention is shown. Fig.42A are ex situ XRD patterns of the positive electrode active material of one embodiment of the present invention in the first, second, fifth, and 50th charging states when charged to 4.7 V. Fig.42B This is an enlarged view of the 2θ range of 18° or more and 21° or less. Fig.42C This is an enlarged view of the 2θ range of 42° or more and 48° or less. FIG. 42A to FIG. 42C The ex situ XRD patterns of the positive electrode including the positive electrode active material according to one embodiment of the present invention in a charged state of 4.5 V, 4.6 V, or 4.7 V are shown.

[0368] FIG. 42A to FIG. 42C The ex situ XRD pattern of the positive electrode including the positive electrode active material of one embodiment of the present invention at the first charge of 4.7 V is shown, which is equivalent to 220.1 mAh / g (Li x Surprisingly, the ex situ XRD pattern of the positive electrode active material of one embodiment of the present invention charged to 4.7 V showed an overlap of two diffraction patterns from the O3 phase, and no diffraction pattern corresponding to the H1-3 phase was observed.

[0369] The diffraction pattern of the first O3 phase has peaks at 2θ=19.0° and 45.3° on the low-angle side, and the diffraction pattern of the second O3 phase has peaks at 2θ=19.2° and 45.5° on the high-angle side. The first O3 phase is equivalent to the existing O3 phase after delithiation. This classification is based on FIG. 44A to FIG. 44C In the charging state shown, the diffraction peak continuously drifts from 4.5V to 4.7V. Fig.44A Ex situ XRD patterns of positive electrodes including the positive electrode active material according to one embodiment of the present invention, which were charged to 4.5 V, 4.6 V, or 4.7 V at 10 mA / g, are shown. Fig.44BThis is an enlarged view of the 2θ range of 18° or more and 21° or less. Fig.44C This is an enlarged view of the 2θ range of 42° or more and 48° or less.

[0370] The second O3 phase is considered to be a different phase having a smaller unit cell volume and the same symmetry as the O3 phase. In this specification, etc., this phase is referred to as "O3' phase".

[0371] The second charge capacity is 215.4mAh / g (Li x In the second charge, the area intensity ratio of the diffraction peak related to the O3' phase increases, and the peak position drifts to the high angle side. The drift of the peak to the high angle side indicates a decrease in the volume of the unit cell, which means a decrease in the lithium concentration in the lithium cobalt oxide. This contradicts the lithium concentration in the first and second charges inferred from the electrochemically observed capacity (first time: x=0.20, second time: x=0.21). It is worth noting that during the first charge, in addition to lithium detachment, the charge may also be consumed due to the decomposition of the electrolyte caused by the formation of SEI confirmed from the Coulomb efficiency.

[0372] Therefore, it can be considered that the actual lithium concentration in the first charge is higher than the lithium concentration inferred from the capacity (x=0.20), and probably also higher than the actual lithium concentration in the second charge. After the fifth charge at a capacity of 225.3 mAh / g (x=0.18), the O3' phase appears as a single phase, and the diffraction peak drifts to a higher angle as the charge capacity increases from the second charge.

[0373] After the 50th charge at a capacity of 214.5 mAh / g (x=0.22), a weaker diffraction peak associated with the H1-3 phase was detected, but the O3' phase still remained.

[0374] 《dQ / dV Curve》 Fig.45 The dQ / dV curves of the positive electrode active material of one embodiment of the present invention in the first cycle, the fifth cycle, and the 50th cycle are shown. In the dQ / dV measurement, the voltage range is 2.5V to 4.7V, the current is 10mA / g, a half cell is used, and the measurement temperature is set to 25°C. Before the dQ / dV measurement, the voltage range is 2.5V to 4.7V (vs. Li + / Li) in the voltage range of the fifth cycle or the 50th cycle, CCCV charging (100mA / g, final current 10mA / g) and CC discharge (100mA / g) were used to cycle the battery 4 times or 49 times at 25°C, respectively. A 10-minute rest time was set after each charging and discharging step. A large voltage polarization was observed in the first cycle, which is consistent with the low capacity of the first cycle in the cycle performance test. The voltage polarization became smaller in the fifth cycle, and the voltage polarization remained small in the 50th cycle. In the dQ / dV curves of the fifth cycle and the 50th cycle, the charging and discharging of the positive electrode active material of one embodiment of the present invention at 25°C both showed reversible peaks at a voltage greater than 4.5V.

[0375] like Fig.45 As shown, the dQ / dV curve of the positive electrode active material of one embodiment of the present invention exhibits a reversible peak at a voltage higher than 4.5 V during charge and discharge, indicating that the phase transition from the O3 phase to the O3' phase is continuously reversible.

[0376] Rietveld Precision The lattice constant of the O3' phase was determined by Rietveld refinement of the XRD patterns of the first and fifth charge cycles as described in detail in Tables 7 and 8. The c-axis lattice constant of the positive electrode active material of one embodiment of the present invention is extremely small compared to the values ​​reported in previous studies on highly delithiated O3 phases (Non-Patent Document 18, etc.).

[0377] [Table 7] Positive electrode active material according to one embodiment of the present invention 4.7v first charge Charging capacity 220.1mAh / g Li x CoO2(x=0.20)

[0378] [Table 8] Positive electrode active material according to one embodiment of the present invention 4.7V fifth charge Charging capacity 225.3mAh / g Li x CoO2(x=0.18)

[0379] The equivalent isotropic temperature factor (Beq) used in the Rietveld refinement is constant, and Li=1.105, Co=0.371, and O=0.552 are used. The charge capacity before the ex situ XRD measurement is used in the calculation of the site occupancy of Li ions. The site occupancy of O ions and Co ions is 1.

[0380] 《Conditional settings for adding elements》 In this specification, etc., it is assumed that the deviation of the CoO2 flat plate is suppressed due to the effect of magnesium as a pillar in the positive electrode active material of one embodiment of the present invention. In order to verify this assumption, the cycle performance of the positive electrode containing M-LCO, MF-LCO, FA-LCO, FN-LCO, FNA-LCO and the positive electrode active material of one embodiment of the present invention is combined with exsitu XRD measurement in a high charge state and evaluated.

[0381] FIG. 46A to FIG. 47B Ex situ XRD patterns and cycle performances of M-LCO, MF-LCO, and a positive electrode active material according to one embodiment of the present invention are shown. Fig.46A Shown are ex situ XRD patterns of positive electrodes including M-LCO, MF-LCO, and the positive electrode active material of one embodiment of the present invention, which were charged to 4.6 V at 4 mA / g. Fig.46B This is an enlarged view of the 2θ range from 18° to 21°. Fig.46C It is an enlarged view with a 2θ range of 42° to 48°. Fig.47A Shows 2.5V to 4.6V (vs.Li + / Li) at 25°C, Fig.47B Shows 2.5V to 4.7V (vs.Li + The cycling performance at 25°C within the voltage range of 1.5V / Li.

[0382] FIG. 48A to FIG. 49B Shown are ex situ XRD patterns and cycle performances of FN-LCO, FA-LCO, FNA-LCO, and a positive electrode active material according to one embodiment of the present invention. Fig.48A Ex situ XRD patterns of positive electrodes including FN-LCO, FA-LCO, FNA-LCO, and the positive electrode active material of one embodiment of the present invention, which were charged to 4.6 V at 4 mA / g, are shown. Fig.48B This is an enlarged view of the 2θ range from 18° to 21°. Fig.48C It is an enlarged view with a 2θ range of 42° to 48°. Fig.49A Shown at 2.5V to 4.6V (vs.Li + / Li) at 25°C, Fig.49B Shows 2.5V to 4.7V (vs.Li + / Li) at 25°C. Fig.47A , Fig.47B and FIG. 49A to FIG. 52BIn the figure, the black marks represent the discharge capacity, and the blank marks represent the coulombic efficiency. The coulombic efficiency of the measurement point with a discharge capacity less than 25 mAh / g is not plotted.

[0383] In order to perform ex situ XRD measurement on the positive electrode including M-LCO, MF-LCO, FN-LCO, FA-LCO, FNA-LCO and the positive electrode active material of one embodiment of the present invention, CCCV charge (40 mA / g, final current 10 mA / g) and CC discharge (40 mA / g) were cycled once in the voltage range of 2.5 V to 4.5 V (vs. Li + / Li). Before ex situ XRD measurement, the battery was charged to 4.6 V with CC (4 mA / g).

[0384] Only MF-LCO and the positive electrode active material of one embodiment of the present invention exhibited good cycle performance and did not exhibit the H1-3 phase. Therefore, the formation of the O3′ phase is caused by the introduction of magnesium due to the treatment using the fluoride molten salt.

[0385] In order to investigate the effect of LiF alone, the cycle characteristics of heated LCO, F-LCO, FNA-LCO, and NA-LCO were measured.

[0386] Fig.50A The voltage range (vs. Li + / Li) with original LCO, heated LCO and F-LCO, Fig.50B The voltage range is shown in 2.5V to 4.7V (vs.Li + / Li) cycle performance.

[0387] Fig.51A The positive electrode active material of NA-LCO, FNA-LCO and one embodiment of the present invention shows the voltage range of 2.5 V to 4.6 V at 25°C (vs. Li + / Li) cycle performance, Fig.51B The voltage range is shown in 2.5V to 4.7V (vs.Li + The coulombic efficiency at the measurement point where the discharge capacity is less than 25 mAh / g is not plotted.

[0388] like FIG. 50A to FIG. 51B As shown, the improvement in charge-discharge cycle characteristics due to the addition of LiF without MgF2 is small.

[0389] like Figure 6As shown in the figure, in the highly delithiated state, the presence of magnesium substituted in the lithium layer provides structural support and prevents the sliding of the CoO2 layer and the phase transition from the O3 phase to the H1-3 phase. In addition, the sliding probably starts from the surface of LCO, so it is possible that the presence of the magnesium-rich rock salt region in the surface layer of the positive electrode active material of one embodiment of the present invention is suppressed. The sliding of the layer is suppressed, and the result is as shown in the SEM after the cycle ( FIG. 38E to FIG. 38H ) and STEM( Fig.40C ) shows that the surface layer of the positive electrode active material of one embodiment of the present invention is not easily degraded and lithium diffusion is not hindered, so it can show good rate and cycle characteristics.

[0390] MFN-LCO and MFA-LCO were synthesized by adding MgF2-LiF-Ni(OH)2 and MgF2-LiF-Al(OH)3 in the same process as that of the positive electrode active material of one embodiment of the present invention.

[0391] Fig.52A The voltage range of pristine LCO, MFN-LCO, MFA-LCO and the positive electrode active material of one embodiment of the present invention at 25°C is 2.5V to 4.6V (vs. Li + / Li) cycle performance, Fig.52B The voltage range is shown in 2.5V to 4.7V (vs.Li + / Li) cycle performance.

[0392] like Fig.52A and Fig.52B As shown, it can be seen that the samples containing both nickel and aluminum together with magnesium and fluorine exhibit the best capacity retention rate. This is because the positive electrode active material of one embodiment of the present invention exhibits a very high coulombic efficiency (for example, when the efficiency is compared in the third cycle with a cutoff voltage of 4.7V, the positive electrode active material of one embodiment of the present invention is 99.79%, MFN-LCO is 99.48%, and MFA-LCO is 99.34%).

[0393] As described above, in this specification, etc., by using fluoride molten salt as a reaction accelerator, magnesium diffusion and doping from the surface of LCO particles to the bulk are achieved. In addition, the remaining magnesium covers the surface of the positive electrode active material particles of one embodiment of the present invention. Through this innovative invention, the phase transition to the H1-3 phase at a charging voltage of 4.7V is particularly effectively prevented.

[0394] Furthermore, ex situ XRD analysis of the positive electrode active material of one embodiment of the present invention at 4.7 V shows that a different O3 phase (O3' phase) is formed. The surface treatment and magnesium doping suppress the phase transition to the H1-3 phase, resulting in the suppression of crystallinity degradation and cracking after cycling at a cutoff voltage of 4.7 V.

[0395] Fig.53 The Ragone plot shown shows that the positive electrode active material of one embodiment of the present invention has the highest energy density among practical positive electrode materials. Therefore, the positive electrode active material of one embodiment of the present invention has a great influence on the field of high energy density batteries and is expected to contribute to the advancement of mobile electronics.

[0396] In addition, this specification and the like provide extremely valuable insights into the basic mechanism of phase transition caused by cation insertion / extraction. This finding is also applicable to other positive electrode materials that deteriorate due to phase transition. Example 2

[0397] In this example, a half-cell was manufactured using a positive electrode active material of one embodiment of the present invention manufactured in the same manner as in Example 1 under conditions partially different from those in Example 1, and a charge and discharge test was performed under conditions partially different from those in Example 1. In addition, the crystal structure was analyzed by ex situ XRD.

[0398] Half Battery The LCO positive electrode is manufactured by mixing 96wt% of active material, 2wt% of carbon black (DENKA BLACK (registered trademark), manufactured by Denka) as a conductive aid, and 2wt% of polyvinylidene fluoride as a binder. At this time, in order to increase the density of the positive electrode active material layer on the positive electrode current collector, a pressing process is performed using a roller press. The conditions for the pressing process are as follows: after the first pressing (linear pressure 210kN / m), a second pressing (linear pressure 1467kN / m) is performed. The upper and lower rollers of the roller press are both 120°C. The mass loading of the active material is 14.5mg / cm 2 The electrode density is 3.9g / cm 3 about.

[0399] As the electrolyte, 1M LiPF6 was dissolved in ethylene carbonate / diethyl carbonate (EC / DEC=volume ratio 3:7) and 2 wt% of vinylene carbonate (VC).

[0400] A half cell was manufactured in the same manner as in Example 1 except for the above conditions.

[0401] 《Charge and discharge test》 The half-cell manufactured as described above was used for charge and discharge tests. First, a discharge rate test was performed, and then a charge and discharge cycle test was performed directly.

[0402] The conditions of the discharge rate test are described. In the first charge and discharge cycle, constant current charging is performed at 0.2C until about 4.6V, constant voltage charging is performed until the current value reaches 0.05C, and constant current discharge is performed at 0.2C until 3.0V. In the second charge and discharge cycle, constant current charging is performed at 0.5C until about 4.6V, constant voltage charging is performed until the current value reaches 0.05C, and constant current discharge is performed at 0.1C until 3.0V. In the third charge and discharge cycle, constant current charging is performed at 0.5C until about 4.6V, constant voltage charging is performed until the current value reaches 0.05C, and constant current discharge is performed at 1.0C until 3.0V. In the fourth charge and discharge cycle, constant current charging is performed at 0.5C until about 4.6V, constant voltage charging is performed until the current value reaches 0.05C, and constant current discharge is performed at 2.0C until 3.0V. Here, 1C is 200 mA / g. In addition, the temperature of the measurement environment was set to 25° C. In addition, the rest time after charging from the end of charging to the start of discharging and the rest time after discharging from the end of discharging to the start of charging were both 10 minutes.

[0403] The conditions of the charge and discharge cycle test are described below. Constant current charging is performed at 0.5C until about 4.6V, and then constant voltage charging is performed until the current value reaches 0.05C. In addition, as a discharge, constant current discharge is performed at 1C until 3.0V. Here, 1C is 200mA / g. In addition, the temperature of the measurement environment is set to 45°C. In addition, the rest time after charging from the end of charging to the start of discharging and the rest time after discharging from the end of discharging to the start of charging are both 10 minutes. In addition, in addition to the end conditions of the above voltage and current values, there is also an end condition of 20 hours for charging and discharging.

[0404] 《Ex situ XRD》 In the above charge and discharge cycle, it was investigated whether the positive electrode active material of one embodiment of the present invention has a crystal structure of lithium cobalt oxide in a discharged state and has an O3′ phase in a charged state.

[0405] In order to analyze the discharge state, a plurality of half-cells subjected to the above-mentioned discharge rate test were prepared. Furthermore, post-discharge XRD measurements were performed under the following three conditions using the above-mentioned charge-discharge cycle test conditions: disassembling the half-cell for XRD measurement after one charge-discharge cycle; disassembling the half-cell for XRD measurement after five charge-discharge cycles; and disassembling the half-cell for XRD measurement after 30 charge-discharge cycles.

[0406] In order to perform the post-charge XRD measurement, a plurality of half-cells subjected to the above-mentioned discharge rate test were prepared. And, the same charge and discharge as the above-mentioned discharge rate test was performed. Then, the post-charge XRD measurement was performed under the following three conditions using the same conditions as the above-mentioned charge and discharge cycle test: disassembling the recharged half-cell for XRD measurement after one cycle of charge and discharge; disassembling the recharged half-cell for XRD measurement after five cycles of charge and discharge; and disassembling the recharged half-cell for XRD measurement after 30 cycles of charge and discharge.

[0407] All measurements were performed by disassembling the half-cell within 1 hour after the discharge or charge was completed. In particular, when disassembling the half-cell in the charged state, since the positive electrode is removed in a state of high voltage charging, it is carefully disassembled using insulating tools so as not to cause a short circuit. In addition, an argon-filled glove box with managed dew point and oxygen concentration is used for disassembly. The dew point of the glove box is preferably below -70°C, and the oxygen concentration is preferably below 5ppm. In addition, when a long time has passed after the above-mentioned charge, the crystal structure of the positive electrode active material may change due to self-discharge, so it is preferably disassembled and analyzed as soon as possible.

[0408] The positive electrode obtained by disassembling the half-cell was placed on a sealable XRD measurement sample holder in the glove box and set on a stage of an XRD device so that the positive electrode could be kept in an argon atmosphere during XRD measurement.

[0409] Then, XRD measurement was started within 15 minutes. The XRD apparatus and conditions were as follows. XRD device: D8 ADVANCE manufactured by Bruker AXS X-ray source: CuKα1 ray Output: 40kV, 40mA Emission angle: Div. Slit, 0.5° Detector: LynxEye Scanning mode: 2θ / θ continuous scanning Measuring range (2θ): 15° to 75° Step width (2θ): set to 0.01° Counting time: 1 second / step Sample stage rotation: 15rpm

[0410] Fig.54 The XRD pattern of the positive electrode after discharge is shown. For comparison, the stoichiometric composition of lithium cobalt oxide LiCoO2 in the O3 phase and the lithium-deficient LiO3 phase are also shown. 0.68 Pattern of CoO2. Fig.55A Show that Fig.54The enlarged graph shows the range between 18° and 21°. Fig.55B Show that Fig.54 The graph is an enlarged graph of the range of 42° or more and 48° or less. It is found that the positive electrode including the positive electrode active material of one embodiment of the present invention has a sharp peak even after 30 cycles at 45° C., and the crystallinity does not decrease after discharge.

[0411] Fig.56 The XRD pattern of the positive electrode after charging is shown. For comparison, the O3' phase, H1-3 phase and O3 (Li 0.35 XRD pattern of CoO2) phase. Fig.57A Show that Fig.56 The enlarged graph shows the range between 18° and 21°. Fig.57B Show that Fig.56 A chart enlarged in the range of 42° or more and 48° or less. The pattern of the positive electrode in the high voltage charging state of the positive electrode active material comprising one embodiment of the present invention is roughly consistent with the reference pattern (O3') of the O3' phase. That is, it is confirmed that the positive electrode active material of one embodiment of the present invention has the O3' phase after charging after one cycle, after charging after five cycles, and after charging after 30 cycles. Therefore, the battery comprising the positive electrode active material of one embodiment of the present invention can maintain the O3' phase even if the number of repeated charge and discharge cycles increases, which can be considered to be one of the reasons for the good charge and discharge cycle characteristics.

Claims

1. A positive electrode active material, comprising: Positive electrode active material particles including surface layer and bulk region, The positive electrode active material particles include lithium cobalt oxide, magnesium, fluorine, nickel and aluminum. The positive electrode active material has a layered rock salt type crystal structure belonging to the space group R-3m in the discharged state, The layered rock salt type crystal structure in the discharge state has more than The lattice constant of the c-axis of the LiCoO2 space group R-3m is 1.4 or less when the GOF is refined by Rietveld fitting. The surface layer includes a magnesium-rich rock salt structure region, Furthermore, the magnesium-rich rock salt structure region is coherently bonded to the bulk region.

2. The positive electrode active material according to claim 1, wherein the lattice constant of the c-axis is less than 3 . The positive electrode active material according to claim 1 , wherein magnesium, fluorine, nickel and aluminum are in the surface layer portion.

4. The positive electrode active material according to claim 1, The volume energy density calculated using the true density of the positive electrode active material is 4250Wh / L or more. Furthermore, the weight energy density calculated using the true density of the positive electrode active material is greater than 865 Wh / kg.

5. A secondary battery comprising: The positive electrode active material according to claim 4; as well as Electrolyte, The electrolyte includes 1M LiPF6 and 5wt% PS dissolved in FEC / MTFP with a volume ratio of 2:

8. 6 . The positive electrode active material according to claim 1 , wherein when a cross section of the positive electrode active material particle is analyzed using an electron probe microanalyzer, an atomic ratio of Mg / Co is 0.005 to 0.015, and an atomic ratio of Al / Co is 0.05 or less.

7. A positive electrode active material comprising: Positive electrode active material particles containing lithium cobalt oxide, magnesium, fluorine, nickel and aluminum, Among them, the bond energy with the maximum intensity shown in the narrow scanning measurement spectrum of Mg1s of the positive active material obtained by X-ray photoelectron spectroscopy is between the bond energy with the maximum intensity shown in the narrow scanning measurement spectrum of Mg1s of magnesium oxide obtained by X-ray photoelectron spectroscopy and the bond energy with the maximum intensity shown in the narrow scanning measurement spectrum of Mg1s of magnesium fluoride obtained by X-ray photoelectron spectroscopy. 8 . The positive electrode active material according to claim 7 , wherein the narrow scan measurement spectrum of Mg1s of the positive electrode active material obtained by X-ray photoelectron spectroscopy exhibits the maximum intensity at a bond energy greater than 1303.3 eV and less than 1306.3 eV. 9 . The positive electrode active material according to claim 8 , wherein when a cross section of the positive electrode active material particle is analyzed using an electron probe microanalyzer, an atomic ratio of Mg / Co is 0.005 to 0.015, and an atomic ratio of Al / Co is 0.05 or less.

10. The positive electrode active material according to claim 7, The positive electrode active material includes a surface portion and a bulk region, And magnesium, fluorine, nickel and aluminum are in the surface layer portion.

11. The positive electrode active material according to claim 7, The volume energy density calculated using the true density of the positive electrode active material is 4250Wh / L or more. Furthermore, the weight energy density calculated using the true density of the positive electrode active material is greater than 865 Wh / kg.

12. A secondary battery comprising: The positive electrode active material according to claim 11; as well as Electrolyte, The electrolyte includes 1M LiPF6 and 5wt% PS dissolved in FEC / MTFP with a volume ratio of 2:

8.

13. A positive electrode active material comprising: Positive electrode active material particles containing lithium cobalt oxide, magnesium, fluorine, nickel and aluminum, The positive electrode active material has a layered rock salt type crystal structure belonging to the space group R-3m in the discharged state. When the positive electrode containing the positive electrode active material in a discharged state is analyzed by X-ray powder diffraction using CuKα1 rays after a charge and discharge cycle test, a peak with a half width of 0.08° or less is detected in the range of 2θ being greater than 18.7° and less than 19.0°, and a peak with a half width of 0.12° or less is detected in the range of 2θ being greater than 45.0° and less than 45.3°, the charge and discharge cycle test being performed under an environment of 25°C on a battery including the positive electrode, lithium metal as a negative electrode, and lithium hexafluorophosphate, ethylene carbonate, and a mixture of diethyl carbonate and 2wt% of vinylene carbonate as an electrolyte, In the charge and discharge cycle test, constant current charging is performed at a current value of 0.5C until the voltage reaches 4.7V, constant voltage charging is performed until the current value reaches 0.05C, and then resting for 10 minutes, and constant current discharge is performed at a current value of 0.5C until the voltage reaches 2.5V, and then resting for 10 minutes. The above charge and discharge cycle is repeated 100 times. And, 1C=200mA / g.

14. The positive electrode active material according to claim 13, The positive electrode active material includes a surface portion and a bulk region, And magnesium, fluorine, nickel and aluminum are in the surface layer portion.

15. The positive electrode active material according to claim 13, The volume energy density calculated using the true density of the positive electrode active material is 4250Wh / L or more. Furthermore, the weight energy density calculated using the true density of the positive electrode active material is greater than 865 Wh / kg.

16. A secondary battery comprising: The positive electrode active material according to claim 15; as well as Electrolyte, The electrolyte includes 1M LiPF6 and 5wt% PS dissolved in FEC / MTFP with a volume ratio of 2:8.